Evaluation of the toxicological screening limit and threshold of toxicological concern in medical device toxicological risk assessment for various patient populations - Shaoping Wu; Jared Wilsey; Matt Lewis; Mao-wen Weng; Yayi Swain; Joelle Hakimi; Junia Pereira; Xiaoling (Sharlene) Dai; Echoleah S. Rufer; Scott Citrowske; Robert Shulfer; Marika Kamberi (Regulatory Toxicology and Pharmacology, 2026)

Extending the protection offered by safe haven networks to threatened non-mammalian fauna - John Gould; Darren Southwell; Andrea S. Griffin; Katherine Moseby; Sarah Legge; Matt W. Hayward (Biological Conservation, 2026)

eDNA-based assessment of microbial dynamics in response to persistent contaminants and degraded water quality in a hypereutrophic urban reservoir - Juliana S. M. Pimentel; Maria Clara V. M. Starling; Camila C. Amorim; Valquíria F. L. Viana; Alessandra S. Martins; Daniel A. S. Rodrigues; Luciana P. M. Brandão; Nadieh de Jonge; Niels O. G. Jørgensen; Louise Schlüter; Matt Simcik; Jeppe Lund Nielsen (Environmental Monitoring and Assessment, 2026)
Urban freshwater ecosystems are increasingly exposed to mixtures of pollutants, including per- and polyfluoroalkyl substances (PFAS). However, their ecological effects remain poorly understood, especially in tropical regions with limited sanitation infrastructure. This study investigated PFAS contamination, water quality, and microbial community structure in Pampulha Lake, a tropical urban reservoir in southeastern Brazil. Spatiotemporal patterns in prokaryotic and eukaryotic diversity were assessed over a year (2022–2023) using environmental DNA metabarcoding of 16S and 18S rRNA genes by integrating taxonomic data with PFAS concentrations and water quality. Physicochemical and multivariate analyses revealed strong seasonal and spatial heterogeneity, influenced by eutrophication, hydrological variability, and pollution gradients. Among the seven PFAS detected above quantification limits, PFBS and PFOA were the most common. Prokaryotic communities showed significant correlations with PFAS, especially with sulfonated forms, while eukaryotic communities were more stable. Diversity patterns highlighted microbial community sensitivity to environmental stress. Overall, results indicate that PFAS influenced microbial assemblages, supporting their inclusion in monitoring frameworks, and eDNA was proved effective for assessing ecological risks in tropical urban reservoirs.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Identifying hotspots of faunal data deficiency to direct urgent research and monitoring - Matt W. Hayward; Danielle Verdon‐Kidd; K. Colyvas; Ellen Saxon; Andrea S. Griffin (Conservation Biology, 2026)
Data deficiency is a substantial challenge for extinction risk assessments because incomplete data means we cannot accurately identify priority protected areas for conservation. Here, we use the International Union for Conservation of Nature (IUCN) distributions of amphibians, sharks and rays, fish, mammals, birds, and reptiles to identify hotspots of data deficient species. We found that areas with high numbers of data deficient species were not randomly distributed and did not necessarily overlap with hotspots of biodiversity, particularly in the Amazon and West Africa. Data deficiency hotspots were concentrated around tropical South America, Africa, and Southeast Asia; however, this distribution varied between taxa. Hotspots of data deficient amphibians were concentrated around the tropical Andean forests of Colombia, Peru, and Ecuador; throughout Brazil; and in the New Guinea Highlands. The tropical forests of the Congo River basin, Papua New Guinea, and the Philippines were hotspots for avian data deficiency. Data deficient chondrichthyans were concentrated in the tropical seas, particularly around the western coast of Africa, East Asia, and the tropical Americas. Indochina was identified as the primary hotspot for data deficient freshwater fish, whereas the Indo‐Pacific was the primary hotspot for data deficient marine fish. Data deficient marine mammals were broadly distributed around the southern oceans, South America, Southeast Asia, and Northwest Africa. Data deficient herpetofauna were concentrated around tropical Asia, whereas tropical South America, Indonesia, and central Africa were the hotspots for data deficient terrestrial mammals. Although data deficiency reflected drivers of biodiversity more broadly (e.g., latitude), other factors were also influential, including the amount of conservation funding invested by a country and population density. Increasing evidence suggests that data deficient species are disproportionately likely to be threatened with extinction. Scientists urgently need to focus their research efforts on these data deficiency hotspots and ensure protected area networks are suitably representative and include data deficient species. Furthermore, the accuracy of status assessments needs to be ascertained, and data deficient species need to be prioritized for study to ensure they are not lost before they are identified.

Functional benefits of soy lecithin supplementation in feeds for channel catfish (Ictalurus punctatus) juveniles: Impacts on production performance, intestinal health, and disease resistance - Crystal L. Conde; Vitor F. Silva; Ana Beatriz de S. Farias; Thiago M. Santana; Jing Huang; Caitlin E. Older; Matt J. Griffin; Peter J. Allen; Fernando Y. Yamamoto (Aquaculture, 2026)

Upcycled glass and plastic bottles offer potential low-cost mitigation to megafauna bycatch in gillnet fisheries - Per Berggren; Joanna Alfaro-Shigueto; Jeffrey C. Mangel; Matt Sharpe; Narriman S. Jiddawi; Jeff Neasham; Gabriel Larre; Andrew J. Temple (Fisheries Research, 2026)

Behavioral variation across multiple phases of intravenous cocaine self-administration among genetically diverse mouse populations - Price E. Dickson; Udita Datta; Troy D. Wilcox; Ashley A. Auth; Robyn L. Ball; Matt Dunn; Heidi S. Fisher; Alyssa Klein; Michael R. Leonardo; Tyler A. Roy; Michael C. Saul; Jason A. Bubier; et al. (Psychopharmacology, 2026)
Genetic and other predisposing factors can influence the progression from initiation of drug intake to compulsive substance use through distinct biobehavioral processes. Operant cocaine self-administration studies in laboratory mice offer a powerful method to dissect the biology of this progression from initiation, dose-response, extinction, and cued reinstatement in a controlled, tractable system. However, many such studies encompass limited genetic diversity and rarely examine self-administration behaviors beyond the acquisition stage. Here, we study three high-diversity mouse populations – 50 strains from the Collaborative Cross (CC) reference panel, a large sample of Diversity Outbred (J: DO) population and their eight founder strains – to characterize the varied phenotypic manifestation of behaviors across multiple phases of cocaine intravenous self-administration (IVSA) in both sexes. We observed distinct strain differences among the founders and CC strains in all phases of self-administration, with heritability estimates ranging from 0 to 0.585 and many CC and J: DO phenotypic values exceeding the range of founders including the C57BL/6J strain. Sex differences were common across behaviors, some manifesting as main effects, others as strain interactions. Finally, by adopting a multi-stage design, we identified extreme strains for various cocaine intake and response traits. Together, these findings demonstrate the utility of extended self-administration protocols in high-diversity mouse populations and establish feasibility for their use in the discovery and characterization of biological mechanisms of substance use traits and for preclinical studies in relevant, complex mouse models.

Risks of concealing environmental degradation - Matt W. Hayward; Kaya Klop‐Toker; Salim Momtaz; Eliza Payne; Louisa Rebec; Robert J. Scanlon; Craig M. Shuttleworth; Nick Valentine; Andrea S. Griffin (Conservation Biology, 2026)
Current practice seeks to conceal the visual impact of land‐use change (i.e., development). Six percent of development impact assessments in Australia and 14% of the World Bank's assessments recommend visual impact mitigation. This mitigation results in, for example, vegetated buffer strips alongside cleared agricultural areas and earthen mounds that block environmental degradation from view. These measures make living alongside such development more palatable, but they conceal its negative effects from the general public. The scale of the problem is global with evidence of mandated regulatory drivers for concealment from around the world. These mitigation measures limit the emotional impact of development on people, reducing their likelihood of implementing pro‐environmental actions. It is important for the populace to see the scale of human impacts on the environment to increase the likelihood of pro‐environmental behaviors and decisions that will help ease the crises facing the environment. We recommend overtly exposing the public to environmental degradation to improve understanding of environmental impacts, increase environmental knowledge, trigger pro‐environmental emotions and actions, and help recalibrate people's understanding of biodiversity loss. Policies and research into the effect of creative public imagery designed to improve communication into environmental destruction while minimizing habituation are important, and ensuring that the “greening” of gray infrastructure yields genuine biodiversity benefits is also critical.

Globally informed and locally refined: Market, management, and carbon projections for the Southeastern United States forest sector - Richard H. Manner; Jinggang Guo; Matt Clutter; Olakunle E. Sodiya; Robert C. Abt; Raymond M. Sheffield; Justin S. Baker (Forest Policy and Economics, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Comparing the fate of agricultural sulfur in two winegrowing regions using paired sulfur stable isotope and microbial community analysis - Laura T. Rea; Nicholas B. Dragone; Matt Oliver; Peter Davidson; Syrie M. Hermans; Niklas J. Lehto; Eve-Lyn S. Hinckley (Science of The Total Environment, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Pollen transport to deep-marine environments: Considerations for reconstructing past vegetation from marine sediment cores - Laura S. McDonald; Lorna J. Strachan; Katherine Holt; Adam D. McArthur; Anthony E. Shorrock; Martin P. Crundwell; Katharina Pank; Madison Clarke; Adam Woodhouse; Davide Gamboa; Jenni L. Hopkins; Matt S. McGlone; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Use of shotgun immunoproteomics for the development of protein vaccines against Edwardsiella piscicida - Kim L. Jacobsen; Matt J. Griffin; Brett S. Phinney; Michelle Salemi; Zeinab Yazdi; Sujita Balami; Caitlin E. Older; Cynthia C. Ware; Fernando Y. Yamamoto; Noor-ul Huda; Tania Rodriguez-Ramos; Brian Dixon; et al. (Fish & Shellfish Immunology, 2026)

The impacts of marine heatwaves on ecosystems and fisheries in Aotearoa New Zealand - Katie M. Cook; Matthew R. Dunn; Erik Behrens; Matt H. Pinkerton; Cliff S. Law; Vonda J. Cummings (New Zealand Journal of Marine and Freshwater Research, 2025)
Marine heatwaves (MHWs) are increasing in frequency and intensity globally, yet the impacts of such extreme events are not well understood. We review the effects of MHWs on the fisheries and ecosystems of Aotearoa‐New Zealand (NZ), an island nation with over 15,000 km of coastline, and 4 million km 2 of exclusive economic zone, that supports diverse marine communities and valuable commercial and recreational fisheries. Using Aotearoa‐NZ and global literature, we discuss the potential effects of MHWs on the physical environment and on species, populations and ecosystems. We review recorded national impacts with a fisheries focus, and systematically assess MHW effects on 32 commercially or culturally important Aotearoa‐NZ wild‐caught fishery or aquaculture species, classifying their vulnerabilities. We found records of MHW‐induced ecosystem shifts, with macroalgae community change, and out‐of‐range occurrences of warm‐water species. Of the 32 species examined, national MHW impacts were documented for three species (green‐lipped mussel, snapper, and Chinook salmon). We highlight the paucity of information for life‐stage specific impacts, and indirect impacts such as changes in predator‐prey interactions and biogenic habitat distributions. Assessing MHW impacts through a fisheries lens highlights the need for enhanced interdisciplinary research and monitoring, to develop sustainable management strategies under environmental change.

Novel evidence of age-related cortical and subcortical constraints in cross-education - Ummatul Siddique; Ashlyn K. Frazer; Jamie Tallent; Oliver Hayman; Justin Andrushko; Matt S. Stock; Joshua Carr; Yonas Akalu; Mohamad Rostami; Sergio Uribe; Simon Walker; Dawson J. Kidgell (GeroScience, 2025)
Cross-education (CE), the phenomenon whereby unilateral strength training induces neuromuscular adaptations in the contralateral limb, is underpinned by distributed cortical and subcortical plasticity. This study evaluated acute neural responses to a single bout of metronome-paced unilateral strength training in younger (n = 17; 27 ± 6 years) and older adults (n = 18; 67 ± 5 years). Neurophysiological assessments included corticospinal excitability and inhibition via transcranial magnetic stimulation (TMS), intracortical inhibition through short-interval intracortical inhibition (SICI), and reticulospinal drive using the StartReact paradigm. Following training, younger adults exhibited a significant reduction in the responsiveness of intracortical inhibitory interneurons, reflected as a release of SICI (pre: 58.05, 95% CI 48.83–67.27; post: 68.88, 95% CI 59.69–78.06; p < 0.01), consistent with diminished GABA- A -mediated synaptic efficacy. In contrast, older adults showed no changes (pre: 65.73, 98% CI 57.00–74.46; post: 60.71, 95% CI 52.03–69.39; p = 0.13), indicating no significant modulation of GABA- A -mediated inhibitory circuits with ageing. No changes in corticospinal excitability were observed in either group. StartReact responses remained stable across timepoints, implying insufficient acute engagement of the reticulospinal tract. Notably, younger adults exhibited a decline in rate of force development (RFD; pre: 912.70, 95% CI 821.97–1003.44 N/s; post: 791.02, 95% CI 700.29–881.75 N/s; p < 0.05), potentially reflecting central fatigue, while older adults displayed no significant change. These findings reveal age-dependent asymmetries in the neural mechanisms underpinning CE, with older adults exhibiting a lack of adaptive modulation in intracortical and subcortical systems. The absence of reticulospinal adaptation underscores the need for sustained or higher-intensity training stimuli to elicit subcortical plasticity. These results inform the development of targeted, age-sensitive neuromuscular rehabilitation strategies. Graphical Abstract

Colin James Webb, BA BSc (Hons) PhD Cantuar. FRSNZ (1949–2023) - Matt S. McGlone; Phil J. Garnock-Jones (New Zealand Journal of Botany, 2025)

A Review of Methionine and Cysteine: Their Roles as Sinks for Reactive Oxygen and Nitrogen Species, Including Bioinformatic Analysis of Their Percent Compositions in Metabolic Proteins - Bethany F. Laatsch; Burhan A. Ali; Anna R. Berthiaume; Grace C. Cunningham; Sabrina M. Duncan; Nathan Hau; Audrey Ho; Marais A. Loomis; Harrison R. Lowater; Brenya L. McNally; Kate L. Mueller; Matt Poppitz; et al. (Indian Journal of Clinical Biochemistry, 2025)

Stacking and Intersecting Nitrogen 4Rs on Potato: Economic Analysis - Samuel H. Stapley; Christopher S. McIntosh; Matt A. Yost; Neil C. Hansen; Ryan C. Christensen; Bryan G. Hopkins (American Journal of Potato Research, 2025)
The 4Rs of nutrient management is an initiative to balance economics with sustainability. The objective was to evaluate individual and stacked 4R practices on potato ( Solanum tuberosum L.) profitability. Treatments included all combinations of two nitrogen (N) sources (urea or polymer coated urea [PCU]), two rates (82 or 100%), and/or two timing/placements (at emergence or split-applied). Gross income and net profit were determined using yields, market sale data, and costs. Total gross income was greatest for PCU split applied and PCU at emergence in 2020 and 2023, respectively. Gross income and net profit were higher for the full rate for PCU compared to urea. The detrimental effect of the reduced rate disappeared with PCU, but not urea. A reduced rate of PCU was similar to a full rate of split applied urea. These data suggest that PCU is a profitable N source for potato even at reduced rates.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Black soldier fly larvae oil as a potential nutraceutical ingredient in diets for hybrid catfish Ictalurus punctatus × I. furcatus juveniles - Ana Beatriz de S. Farias; Thiago M. Santana; Caitlin E. Older; Jing Huang; Heather R. Jordan; Elizabeth G. Affonso; Delbert M. Gatlin; Matt J. Griffin; Fernando Y. Yamamoto; Ligia U. Gonçalves (Aquaculture, 2025)

Moving from single values to trade-off curves for assessing the performance of water resources systems under uncertainty - Yuan Cao; Wenyan Wu; Holger R. Maier; Matt S. Gibbs (Environmental Modelling & Software, 2025)

Temperature‐dependent alterations in the proteome of the emergent fish pathogen Edwardsiella piscicida - Kim L. Jacobsen; Matt Griffin; Brett S. Phinney; Michelle Salemi; Zeinab Yazdi; Sujita Balami; Caitlin E. Older; Esteban Soto (Journal of Fish Diseases, 2025)
Edwardsiella piscicida is an emerging bacterial pathogen and the aetiological agent of edwardsiellosis among cultured and wild fish species globally. The increased frequency of outbreaks of this Gram‐negative, facultative intracellular pathogen pose not only a threat to the aquaculture industry but also a possible foodborne/waterborne public health risk due to the ill‐defined zoonotic potential. Thus, understanding the role of temperature on the virulence of this emerging pathogen is essential for comprehending the pathogenesis of piscine edwardsiellosis in the context of current warming trends associated with climate change, as well as providing insight into its zoonotic potential. In this study, significant temperature‐dependent alterations in bacterial growth patterns were observed, with bacterial isolates grown at 17°C displaying higher peak growth sizes, extended lag times, and slower maximal growth rates than isolates grown at 27or 37°C. When E. piscicida isolates were grown at 37°C compared to 27 and 17°C, mass spectrometry analysis of the E. piscicida proteome revealed significant downregulation of crucial virulence proteins, such as Type VI secretion system proteins and flagellar proteins. Although in vivo models of infection are warranted, this in vitro data suggests possible temperature‐associated alterations in the virulence and pathogenic potential of E. piscicida in poikilotherms and homeotherms.

A commentary on strategic community-led directions for water quality modelling in Australia and New Zealand - Danlu Guo; Anna Lintern; Alexander H. Elliott; Melanie E. Roberts; Susan M. Cuddy; Ulrike Bende-Michl; Baihua Fu; Klaus Joehnk; Robert Sargent; Danswell Starrs; Anthony J. Jakeman; Vaughn Grey; et al. (Journal of Hydrology, 2025)

Black soldier fly (Hermetia illucens) larvae exoskeleton as a potential source of chitin in diets for juvenile channel catfish (Ictalurus punctatus) - Thiago M. Santana; Ana Beatriz de S. Farias; Caitlin E. Older; Nicholas Romano; Delbert M. Gatlin; Matt J. Griffin; Fernando Y. Yamamoto; Ligia U. Gonçalves (Fish Physiology and Biochemistry, 2025)

Ndufs4−/− mice: a testing ground for longevity interventions - Jackson Nuss; Matt Kaeberlein; Alessandro Bitto; Anthony S. Grillo (GeroScience, 2025)
Mice missing the complex I subunit Ndufs4 of the electron transport chain are widely used as a leading animal model of Leigh syndrome, a pediatric neurodegenerative disorder that leads to premature death. More broadly, this animal model has enabled a better understanding of the pathophysiology of mitochondrial disease and mitochondrial dysfunction in sporadic disorders. Intriguingly, longevity interventions are very effective at treating symptoms of disease in this model. Herein, we introduce the model and its notable features that may help provide insights in longevity research. We performed a retrospective analysis of historical data from our laboratories over the past 10 years regarding the use of this animal model in aging studies, the manifestation and progression of mitochondrial disease, and factors that influence their premature death. We observed a correlation between weight and lifespan in female animals and a sex-independent correlation between the onset of clasping, a typical neurodegenerative symptom, and overall survival. We observed a sexual dimorphism in lifespan with female mice being more resilient despite a similar age of onset of disease symptoms. Lastly, we report increased lifespan and delayed onset of disease symptoms following treatment with 17-alpha-estradiol, a non-feminizing estrogen which can extend lifespan in genetically heterogeneous mice. This analysis serves as a useful guide for researchers utilizing this animal in the discovery of effective interventions for longevity and to prevent the onset of disease. It suggests there may be unprecedented underlying sex-specific differences in patients with Leigh syndrome and further strengthens the connection between normative aging and mitochondrial dysfunction.

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Conservation genetics of a freshwater percid, Sander canadensis, in Manitoba, Canada - Caleb H. S. Wong; Matt J. Thorstensen; Scott Forbes; Jens P. C. Franck; Sara V. Good; Geoff M. Klein; Caleb T. Hasler (Conservation Genetics, 2025)

Ichthyofaunal Metabarcoding in the Southern Appalachians: Use of eDNA Metabarcoding in Fish Surveys in Lotic Systems of the Great Smoky Mountains National Park with Comparisons to Historic Electrofishing Data - Ben F. Brammell; Sara A. Brewer; Karsner S. Fetter; Lauren E. Slone; Matt A. Kulp; Ben R. S. McLaughlin (Fishes, 2025)
eDNA appears well positioned to play a significant role in the future of biomonitoring, and the need to assess the efficacy of eDNA-based surveys in a variety of habitats is increasing. We conducted an eDNA metabarcoding-based survey of fish communities in the Great Smoky Mountains National Park (GSMNP), located in eastern Tennessee and western North Carolina. The GSMNP, widely recognized as a biodiversity hotspot, encompasses 211,419 hectares of the Southern Appalachian Mountains with elevations up to 2205 meters and is home to approximately 73 species of fish, including 12 families and three species classified as endangered or threatened. We collected 50 water samples in first to sixth order streams at elevations of 336 to 1462 meters, including all major watersheds found in the park. eDNA was amplified utilizing two primer sets which each target differing regions of the 12S mitochondrial gene and generate amplicons of varying size (97 and 225 bp, respectively), and sequencing was conducted to an expected read depth of 400,000 reads per sample per marker. We detected a total of 40 fish species; of these, 36 were detected with the primer set which produces a 97 bp amplicon, and 12 of these 36 were detected only by this primer set. Species assemblages varied between stream orders, and species richness decreased with increasing elevation and increased with increasing stream order. Significant correlations were observed between biomass data from electrofishing monitoring (1984–2023) and eDNA metabarcoding read counts in five of seven species examined, including all salmonids. eDNA metabarcoding was demonstrated to be effective in assessing fish communities in high-elevation lotic systems in the Southern Appalachians, and our results suggest that primers targeting shorter amplicons may exhibit greater efficacy in these ecosystems.

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Corrigendum to “Incorporating heterogeneity in farmer disease control behaviour into a livestock disease transmission model” Preventive Vet. Med. 219 (2023) 106019 - Edward M. Hill; Naomi S. Prosser; Paul E. Brown; Eamonn Ferguson; Martin J. Green; Jasmeet Kaler; Matt J. Keeling; Michael J. Tildesley (Preventive Veterinary Medicine, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Development of the Late Oligocene Zákupy Diatreme, Czech Republic: New insights into protracted diatreme emplacement - Vladislav Rapprich; Michael S. Petronis; Sarah F. Trevino; Jennifer Lindline; Benjamin van Wyk de Vries; Ondřej Pour; Zuzana Tasáryová; Matt Heizler (Journal of Volcanology and Geothermal Research, 2025)

Patterns and mechanisms of wetland change in the Breton sound estuary, Mississippi River delta: A review - John Day; Robert Lane; Matt Moerschbaecher; H.C. Clark; Mead Allison; Ehab Meselhe; Alexander S. Kolker; Rachael Hunter; Paul Kemp; Jae-Young Ko; Robert Twilley; John R. White; et al. (Estuarine, Coastal and Shelf Science, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Re-examination of archived materials reveals infection of zebra mussels Dreissena polymorpha in UK waters with the parasite Haplosporidium raabei - Rachel Foster; Jasmine E. Hunt; Kelly S. Bateman; Matthew J. Green; William Ball; Matt Longshaw; Laura Heath; Paul Stebbing; Georgia M. Ward (Biological Invasions, 2025)

Role of national regime ideology for predicting biodiversity outcomes - Jacob Jones; Andrea S. Griffin; Frank W. Agbola; Matt W. Hayward (Conservation Biology, 2025)
The rapid decline of global biodiversity has engendered renewed debate about the social, economic, and political factors contributing to it. Specifically, there is little understanding of the role that political ideology within a country (e.g., nationalism, conservatism, socialism) plays in determining biodiversity outcomes. We used negative binomial generalized linear models to investigate the importance of national regime ideology in predicting threatened animal species and protected area establishment compared with other factors that affect biodiversity outcomes, such as gross domestic product, inequality, and democracy. For threatened animals, the model with the highest Akaike weight suggested adverse biodiversity outcomes arose from larger gross domestic product (β = 0.120, p p p p

Capacity and capability of remote sensing to inform invasive plant species management in the Pacific Islands region - Carrol M. H. Chan; Christopher J. Owers; Sascha Fuller; Matt W. Hayward; David Moverley; Andrea S. Griffin (Conservation Biology, 2025)
The Pacific Islands region is home to several of the world's biodiversity hotspots, yet its unique flora and fauna are under threat because of biological invasions. These invasions are likely to proliferate as human activity increases and large‐scale natural disturbances unfold, exacerbated by climate change. Remote sensing data and techniques provide a feasible method to map and monitor invasive plant species and inform invasive plant species management across the Pacific Islands region. We used case studies taken from literature retrieved from Google Scholar, 3 regional agencies’ digital libraries, and 2 online catalogs on invasive plant species management to examine the uptake and challenges faced in the implementation of remote sensing technology in the Pacific region. We synthesized remote sensing techniques and outlined their potential to detect and map invasive plant species based on species phenology, structural characteristics, and image texture algorithms. The application of remote sensing methods to detect invasive plant species was heavily reliant on species ecology, extent of invasion, and available geospatial and remotely sensed image data. However, current mechanisms that support invasive plant species management, including policy frameworks and geospatial data infrastructure, operated in isolation, leading to duplication of efforts and creating unsustainable solutions for the region. For remote sensing to support invasive plant species management in the region, key stakeholders including conservation managers, researchers, and practitioners; funding agencies; and regional organizations must invest, where possible, in the broader geospatial and environmental sector, integrate, and streamline policies and improve capacity and technology access.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Global survey of paleo-bedforms on Mars - Matthew Chojnacki; Lori K. Fenton; Lauren A. Edgar; Mackenzie Day; Christopher S. Edwards; Aaron R. Weintraub; Amber L. Gullikson; Matt W. Telfer (Geomorphology, 2024)

The role of dissolved organic carbon in Great Smoky Mountains National Park streams impacted by long-term acid deposition - Jason R. Brown; John S. Schwartz; Michael E. Essington; Qiang He; Matt A. Kulp; Ian M. Simpson (Environmental Monitoring and Assessment, 2024)

Challenges in collecting information on sexual orientation and gender identity for cancer patients: perspectives of hospital and central cancer registry abstractors - J. L. Sorensen; M. M. West; AM. Racila; O. A. Amao; B. J. Matt; S. Bentler; A. R. Kahl; M. E. Charlton; A. T. Seaman; S. H. Nash (Cancer Causes & Control, 2024)

Diversity in clinical isolates of Ictalurid herpesvirus 1 ( IcHV1 ) from U.S. farm‐raised catfish and virulence assessment in channel and channel × blue catfish hybrids - Arun Venugopalan; Danielle White; Adrián López‐Porras; Lorelei Ford; Cynthia Ware; Marsha A. Lewis; James M. Steadman; Lester H. Khoo; Bradley Richardson; Charles M. Walker; Todd S. Byars; David J. Wise; et al. (Journal of Fish Diseases, 2024)
Ictalurid herpesvirus 1 (IcHV1) is the most significant viral agent in U.S. catfish aquaculture. Little is known regarding the genetic stability and antigenic variability of IcHV1. Herein, the genetic and antigenic diversity of IcHV1 field isolates was assessed by restriction fragment length polymorphism (RFLP) analysis and serum neutralization assays. RFLP analysis identified two distinct genotypes (IcHV1A and IcHV1B), both discrete from blue catfish alloherpesvirus (BCAHV). Neutralization assays with anti‐IcHV1 monoclonal antibody Mab‐95 indicate shared antigenic determinants for IcHV1A and IcHV1B that are absent from BCAHV, which Mab‐95 did not neutralize. Virulence assessments with representative isolates demonstrate significant differences between isolates within RFLP groups and pooled RFLP group data suggest IcHV1B (pooled survival [mean ± SE]: 58.3% ± 2.6) may be more virulent than IcHV1A (survival: 68.6% ± 2.4). Rechallenges with representative IcHV1A and IcHV1B isolates indicate a cross‐protective effect, with fish surviving initial exposure to IcHV1A or IcHV1B showing robust protection when subsequently re‐exposed to IcHV1A or IcHV1B. This work demonstrated significant differences in virulence between case isolates, identifying two discrete IcHV1 lineages, distinct from BCAHV, with similar virulence in channel and channel × blue catfish hybrids and a cross‐protective effect in catfish surviving exposure to either lineage.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Modernizing the US National Fire Danger Rating System (version 4): Simplified fuel models and improved live and dead fuel moisture calculations - W. Matt Jolly; Patrick H. Freeborn; Larry S. Bradshaw; Jon Wallace; Stuart Brittain (Environmental Modelling & Software, 2024)

Ecosourcing for resilience in a changing environment - Peter B. Heenan; William G. Lee; Matt S. McGlone; James K. McCarthy; Caroline M. Mitchell; Matthew J. Larcombe; Gary J. Houliston (New Zealand Journal of Botany, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Complementary classifications of aeolian dunes based on morphology, dynamics, and fluid mechanics - Sylvain Courrech du Pont; David M. Rubin; Clément Narteau; Mathieu G.A. Lapôtre; Mackenzie Day; Philippe Claudin; Ian Livingstone; Matt W. Telfer; Jani Radebaugh; Cyril Gadal; Andrew Gunn; Patrick A. Hesp; et al. (Earth-Science Reviews, 2024)

Morphological and molecular data establishes Clinostomum dolichorchum n. sp. (Digenea: Clinostomidae) in the great blue heron Ardea herodias L. and American bullfrog Rana catesbeiana Shaw - Jonah A. Nguyen; Ethan T. Woodyard; Chris T. McAllister; Susan V. Marcquenski; Divya Rose; Celene M. Slifka; Logan R. S. Robison; Matt J. Griffin; T. Graham Rosser (Systematic Parasitology, 2024)

Integrated organismal responses induced by projected levels of CO 2 and temperature exposures in the early life stages of lake sturgeon - Luke D. Belding; Matt J. Thorstensen; Alex R. Quijada‐Rodriguez; William S. Bugg; Gwangseok R. Yoon; Alison R. Loeppky; Garrett J. P. Allen; Alexandra N. Schoen; Madison L. Earhart; Catherine Brandt; Jennifer L. Ali; Dirk Weihrauch; et al. (Molecular Ecology, 2024)
Atmospheric CO 2 and temperature are rising concurrently, and may have profound impacts on the transcriptional, physiological and behavioural responses of aquatic organisms. Further, spring snowmelt may cause transient increases of p CO 2 in many freshwater systems. We examined the behavioural, physiological and transcriptomic responses of an ancient fish, the lake sturgeon ( Acipenser fulvescens ) to projected levels of warming and p CO 2 during its most vulnerable period of life, the first year. Specifically, larval fish were raised in either low (16°C) or high (22°C) temperature, and/or low (1000 μatm) or high (2500 μatm) p CO 2 in a crossed experimental design over approximately 8 months. Following overwintering, lake sturgeon were exposed to a transient increase in p CO 2 of 10,000 μatm, simulating a spring melt based on data in freshwater systems. Transcriptional analyses revealed potential connections to otolith formation and reduced growth in fish exposed to high p CO 2 and temperature in combination. Network analyses of differential gene expression revealed different biological processes among the different treatments on the edges of transcriptional networks. Na + /K + ‐ATPase activity increased in fish not exposed to elevated p CO 2 during development, and mRNA abundance of the β subunit was most strongly predictive of enzyme activity. Behavioural assays revealed a decrease in total activity following an acute CO 2 exposure. These results demonstrate compensatory and compounding mechanisms of p CO 2 and warming dependent on developmental conditions in lake sturgeon. Conserved elements of the cellular stress response across all organisms provide key information for how other freshwater organisms may respond to future climate change.

The companion dog as a model for inflammaging: a cross-sectional pilot study - Sarah M. Schmid; Jessica M. Hoffman; Jena Prescott; Holley Ernst; Daniel E. L. Promislow; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; et al. (GeroScience, 2024)

fNIRS is capable of distinguishing laterality of lower body contractions - Rob J. MacLennan; Jesus A. Hernandez-Sarabia; Shawn M. Reese; JoCarol E. Shields; Claire M. Smith; Katharina Stute; Jordyn Collyar; Alex A. Olmos; Tyler L. Danielson; Demi L. MacLennan; Jason I. Pagan; Ryan M. Girts; et al. (Experimental Brain Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Environmental driving forces and phytoplankton diversity across the Ross Sea region during a summer–autumn transition - Antonia Cristi; Cliff S. Law; Matt Pinkerton; Adriana Lopes dos Santos; Karl Safi; Andres Gutiérrez‐Rodríguez (Limnology and Oceanography, 2024)
The Ross Sea is a highly productive system characterized by a seasonal succession of phytoplankton groups. However, most of the current understanding is based on observations on the continental shelf in spring and summer at relatively coarse taxonomic resolution. Here, we characterize community composition (class to species) using V4‐18S rRNA gene metabarcoding on transects to and across the Ross Sea (shelf‐slope and oceanic subregions) during two voyages covering the Austral summer–autumn progression in successive years. Phytoplankton composition shifted from low‐diversity diatom‐dominated (50%) communities during the summer to more diverse dinoflagellate‐dominated (48%) systems during the lower‐productivity autumn season. Prymnesiophyceae abundance was low on both voyages (10%), except on the southeast shelf‐slope, where Phaeocystis antarctica dominated a shallow mixed layer, contrary to its reported preference for deep‐mixing conditions. Amplicon sequence variant analysis identified distinct spatial patterns for two P. antarctica genotypes yet clustered certain species of Bacillariophyta and Prymnesiophyceae, indicating similar environmental preference for genotypes in these groups. Multivariate analysis of environmental drivers found a higher correlation of community composition variation with salinity and macronutrients, but less so with mixed layer depth, considered a primary determinant of taxonomic composition in the Ross Sea. Comparison between years established that community composition was temporally more stable in oceanic relative to shelf‐slope waters. This study of seasonal variation of phytoplankton community composition at finer taxonomic resolution provided insights into species‐ and strain‐specific distribution, ecological preferences, and relationships to environmental conditions in the wider Ross Sea to inform modeling and projection of future regional changes.

Occurrence of antibiotics, hormones and PFAs in surface water from a Nile tilapia aquaculture facility in a Brazilian hydroelectric reservoir - Daniel Aparecido da S. Rodrigues; Maria Clara V.M. Starling; André Luiz C. de Barros; Mônica C. Santos; Eloísa Stéphanie da Silva; Guenther Carlos C. Viana; Lara Fabian da S. Ribeiro; Matt F. Simcik; Camila C. Amorim (Chemosphere, 2024)

A method for the systematic selection of enzyme panel candidates by solving the maximum diversity problem - Christian Atallah; Katherine James; Zhen Ou; James Skelton; David Markham; Matt S. Burridge; James Finnigan; Simon Charnock; Anil Wipat (BioSystems, 2024)

Metrics and Considerations for Evaluating How Forest Treatments Alter Wildfire Behavior and Effects - Anthony G Vorster; Camille Stevens-Rumann; Nicholas Young; Brian Woodward; Christopher Tsz Hin Choi; Marin E Chambers; Antony S Cheng; Michael Caggiano; Courtney Schultz; Matthew Thompson; Michelle Greiner; Greg Aplet; et al. (Journal of Forestry, 2024)
The influence of forest treatments on wildfire effects is challenging to interpret. This is, in part, because the impact forest treatments have on wildfire can be slight and variable across many factors. Effectiveness of a treatment also depends on the metric considered. We present and define human–fire interaction, fire behavior, and ecological metrics of forest treatment effects on wildfire and discuss important considerations and recommendations for evaluating treatments. We demonstrate these concepts using a case study from the Cameron Peak Fire in Colorado, USA. Pre-fire forest treatments generally, but not always, experienced reduced burn severity, particularly when surface fuels were reduced. Treatments in the Cameron Peak Fire have also been documented as increasing tree survivorship, aiding suppression efforts, promoting firefighter safety, and influencing fire spread. However, the impacts of pre-fire management on primary landscape-scale objectives, like watershed protection, are unknown. Discussions about the influence of pre-fire treatments on fire effects must define the indicator(s) being assessed, as the same treatment may be considered successful under one measure but not others. Thus, it is critical to bring a common language and understanding to conversations about treatment effects and advance efforts to evaluate the range of treatment effects, thus supporting treatment planning.

Genotypic variation, phylogeography, unified species concept, and the ‘grey zone’ of taxonomic uncertainty in kānuka: recognition of Kunzea ericoides (A.Rich.) Joy Thomps. sens. lat. (Myrtaceae) - Peter B. Heenan; Matt S. McGlone; Caroline M. Mitchell; James K. McCarthy; Gary J. Houliston (New Zealand Journal of Botany, 2024)

An mmWave radar-based mass flow sensor using machine learning towards a peanut yield monitor - Rafael Bidese-Puhl; Christopher L. Butts; Matt Rewis; Joseph S. McIntyre; Jason Morris; Bennie Branch; Yin Bao (Computers and Electronics in Agriculture, 2023)

Utility of wastewater genomic surveillance compared to clinical surveillance to track the spread of the SARS-CoV-2 Omicron variant across England - Franziska S. Brunner; Alexander Payne; Edward Cairns; George Airey; Richard Gregory; Natalie D. Pickwell; Myles Wilson; Matthew Carlile; Nadine Holmes; Verity Hill; Harry Child; Jasmine Tomlinson; et al. (Water Research, 2023)

An agent-based model to quantify energetics, movement and habitat selection of mid-continent mallards in the Mississippi Alluvial Valley - Florian G. Weller; Elisabeth B. Webb; Sean Fogenburg; William S. Beatty; Dylan Kesler; Robert H. Blenk; Kevin M. Ringelman; Matt L. Miller; Céline Arzel; John M. Eadie (Ecological Modelling, 2023)

Sexual systems in the New Zealand angiosperm flora - Matt S. McGlone; Sarah J. Richardson (New Zealand Journal of Botany, 2023)

Incorporating heterogeneity in farmer disease control behaviour into a livestock disease transmission model - Edward M. Hill; Naomi S. Prosser; Paul E. Brown; Eamonn Ferguson; Martin J. Green; Jasmeet Kaler; Matt J. Keeling; Michael J. Tildesley (Preventive Veterinary Medicine, 2023)

A comparison of techniques for verifying the accuracy of precision decomposition-derived relationships between motor unit firing rates and recruitment thresholds from surface EMG signals - Jonathan P. Beausejour; Paul Bohlen; Kylie K. Harmon; Ryan M. Girts; Jason I. Pagan; Debbie L. Hahs-Vaughn; Trent J. Herda; Matt S. Stock (Experimental Brain Research, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Elevated temperatures reduce population‐specific transcriptional plasticity in developing lake sturgeon ( Acipenser fulvescens ) - William S. Bugg; Matt J. Thorstensen; Katie E. Marshall; W. Gary Anderson; Ken M. Jeffries (Molecular Ecology, 2023)
Rising mean and variance in temperatures elevates threats to endangered freshwater species such as lake sturgeon, Acipenser fulvescens . Previous research demonstrated that higher temperatures during development result in physiological consequences for lake sturgeon populations throughout Manitoba, Canada, with alteration of metabolic rate, thermal tolerance, transcriptional responses, growth and mortality. We acclimated lake sturgeon (30–60 days post fertilization, a period of high mortality) from northern and southern populations (56°02′46.5″N, 96°54′18.6″W and 50°17′52″N, 95°32′51″W, respectively, separated by approximately 650 km) within Manitoba to current (summer highs of 20–23°C) and future projected (+2–3°C) environmental temperatures of 16, 20 and 24°C for 30 days, and we measured gill transcriptional responses using RNAseq. Transcripts revealed SNPs consistent with genetically distinct populations and transcriptional responses altered by acclimation temperature. There were a higher number of differentially expressed transcripts observed in the southern, compared to the northern, population as temperatures increased, indicating enhanced transcriptional plasticity. Both lake sturgeon populations responded to elevated acclimation temperatures by downregulating the transcription of genes involved in protein synthesis and energy production. Furthermore, there were population‐specific thresholds for the downregulation of processes promoting transcriptional plasticity as well as mitochondrial function as the northern population showed decreases at 20°C, while this capacity was not diminished until 24°C in the southern population. These transcriptional responses highlight the molecular impacts of increasing temperatures for divergent lake sturgeon populations during vulnerable developmental periods and the critical influence of transcriptome plasticity on acclimation capacity.

Evaluation of off-label rapamycin use to promote healthspan in 333 adults - Tammi L. Kaeberlein; Alan S. Green; George Haddad; Johnny Hudson; Anar Isman; Andy Nyquist; Bradley S. Rosen; Yousin Suh; Sajad Zalzala; Xingyu Zhang; Mikhail V. Blagosklonny; Jonathan Y. An; et al. (GeroScience, 2023)

Associations between physical activity and cognitive dysfunction in older companion dogs: results from the Dog Aging Project - Emily E. Bray; David A. Raichlen; Kiersten K. Forsyth; Daniel E. L. Promislow; Gene E. Alexander; Evan L. MacLean; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; et al. (GeroScience, 2023)

DiceCT for fishes: recommendations for pairing iodine contrast agents with μCT to visualize soft tissues in fishes - Matthew A. Kolmann; Ramon S. Nagesan; James V. Andrews; Samuel R. Borstein; Rodrigo Tinoco Figueroa; Randal A. Singer; Matt Friedman; Hernán López‐Fernández (Journal of Fish Biology, 2023)
Computed tomography (CT) scanning and other high‐throughput three‐dimensional (3D) visualization tools are transforming the ways we study morphology, ecology and evolutionary biology research beyond generating vast digital repositories of anatomical data. Contrast‐enhanced chemical staining methods, which render soft tissues radio‐opaque when coupled with CT scanning, encompass several approaches that are growing in popularity and versatility. Of these, the various diceCT techniques that use an iodine‐based solution like Lugol's have provided access to an array of morphological data sets spanning extant vertebrate lineages. This contribution outlines straightforward means for applying diceCT techniques to preserved museum specimens of cartilaginous and bony fishes, collectively representing half of vertebrate species diversity. This study contrasts the benefits of using either aqueous or ethylic Lugol's solutions and reports few differences between these methods with respect to the time required to achieve optimal tissue contrast. It also explores differences in minimum stain duration required for different body sizes and shapes and provides recommendations for staining specimens individually or in small batches. As reported by earlier studies, the authors note a decrease in pH during staining with either aqueous or ethylic Lugol's. Nonetheless, they could not replicate the drastic declines in pH reported elsewhere. They provide recommendations for researchers and collections staff on how to incorporate diceCT into existing curatorial practices, while offsetting risk to specimens. Finally, they outline how diceCT with Lugol's can aid ichthyologists of all kinds in visualizing anatomical structures of interest: from brains and gizzards to gas bladders and pharyngeal jaw muscles.

Banking on a new understanding: translational opportunities from veterinary biobanks - D. LaLonde-Paul; L. Mouttham; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; Virginia R. Fajt; Annette L. Fitzpatrick; Unity Jeffery; et al. (GeroScience, 2023)

Problems with Paranthropus - Matt Sponheimer; David J. Daegling; Peter S. Ungar; René Bobe; Oliver C.C. Paine (Quaternary International, 2023)

A global review of problematic and pathogenic parasites of farmed tilapia - Andrew P. Shinn; Annemarie Avenant‐Oldewage; Melba G. Bondad‐Reantaso; Armando J. Cruz‐Laufer; Adriana García‐Vásquez; Jesús S. Hernández‐Orts; Roman Kuchta; Matt Longshaw; Matthijs Metselaar; Antoine Pariselle; Gerardo Pérez‐Ponce de León; Pravata Kumar Pradhan; et al. (Reviews in Aquaculture, 2023)
Over the past 80 years, tilapia have been translocated globally for aquaculture; active production is recorded in >124 countries. Of 7 million tonnes of tilapia produced in aquaculture, 79% is from 79 countries outside the natural range of tilapia. Capture fisheries account for a further 723,627 tonnes of tilapia, and >47% of this is landed from established invasive populations outside Africa. Tilapias host a rich fauna of parasites, many of which have been translocated with their hosts. This review summarises >2500 host–parasite records from 73+ countries and >820 recorded tilapia translocations (provided in the supplementary materials). This work focuses on the notable pathogens that threaten the health of cultured populations of tilapia, providing a description of their pathology and includes species that also have substantial impacts on wild tilapia populations, where relevant. For each major parasite taxonomic group, we highlight which parasites have been translocated or have been acquired from the new environments into which tilapia have been introduced, together with remarks on standard treatment approaches and research on them and their management and control. Regarding the theme ‘Tilapia health: quo vadis ?’, Africa has enormous potential for aquaculture growth, but substantial knowledge gaps about tilapia parasites in many African states remain, which creates associated production and biosecurity risks. For each parasitic group, therefore, the risks of parasite translocation to new regions as tilapia aquaculture industries expand are highlighted.

Vertical deformation and residual altimeter systematic errors around continental Australia inferred from a Kalman-based approach - Mohammad-Hadi Rezvani; Christopher S. Watson; Matt A. King (Journal of Geodesy, 2022)
We further developed a space–time Kalman approach to investigate time-fixed and time-variable signals in vertical land motion (VLM) and residual altimeter systematic errors around the Australian coast, through combining multi-mission absolute sea-level (ASL), relative sea-level from tide gauges (TGs) and Global Positioning System (GPS) height time series. Our results confirmed coastal subsidence in broad agreement with GPS velocities and unexplained by glacial isostatic adjustment alone. VLM determined at individual TGs differs from spatially interpolated GPS velocities by up to ~ 1.5 mm/year, yielding a ~ 40% reduction in RMSE of geographic ASL variability at TGs around Australia. Our mission-specific altimeter error estimates are small but significant (typically within ~ ± 0.5–1.0 mm/year), with negligible effect on the average ASL rate. Our circum-Australia ASL rate is higher than previous results, suggesting an acceleration in the ~ 27-year time series. Analysis of the time-variability of altimeter errors confirmed stability for most missions except for Jason-2 with an anomaly reaching ~ 2.8 mm/year in the first ~ 3.5 years of operation, supported by analysis from the Bass Strait altimeter validation facility. Data predominantly from the reference missions and located well off narrow shelf regions was shown to bias results by as much as ~ 0.5 mm/year and highlights that residual oceanographic signals remain a fundamental limitation. Incorporating non-reference-mission measurements well on the shelf helped to mitigate this effect. Comparing stacked nonlinear VLM estimates and altimeter systematic errors with the El Niño-Southern Oscillation shows weak correlation and suggests our approach improves the ability to explore nonlinear localized signals and is suitable for other regional- and global-scale studies.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Development of a ddPCR assay for the detection of the Smoky Madtom (Noturus baileyi) from eDNA in stream water samples - Aaron W. Aunins; Michael S. Eackles; Paul E. Super; Matt A. Kulp; Becky J. Nichols; Barbara A. Lubinski; Cheryl L. Morrison; Tim L. King (Conservation Genetics Resources, 2022)
The Smoky Madtom Noturus baileyi is a federally endangered species, whose native distribution includes lower Abrams Creek in Great Smoky Mountains National Park (GRSM) and Citico Creek in nearby Cherokee National Forest. Due to challenges for bio-monitoring posed by its nocturnality and cryptic life history, an environmental DNA (eDNA)-based approach for detection would be useful to complement existing electrofishing and seining efforts to better understand the distribution of this species. We developed a probe-based droplet digital PCR (ddPCR) assay to detect Smoky Madtoms from non-invasively collected water samples. The assay was specific to N. baileyi and did not amplify concentrated genomic DNA of 16 co-occurring or regional fish species, including the yellowfin madtom N. flavipinnis and stonecat N. flavus . The assay limit of detection (LOD) was determined to be 4.18 copies (95% CI: 3.95, 4.41). Several 2 L water samples collected from throughout various streams in GRSM in 2016 and 2017 were tested for the presence of N. baileyi using the ddPCR assay. N. baileyi was detected at two different sites in 2016 and 2017 within Abrams Creek previously known to contain N. baileyi , but no novel detections in other sampled streams were observed. This assay should prove useful for continued surveys of N. baileyi in GRSM.

Proposal to ‘restore’ indigenous names misunderstands the complementary nature of botanical nomenclature and indigenous vernacular plant names - Matt S. McGlone; Peter B. Heenan; Aaron D. Wilton; Atholl Anderson (New Zealand Journal of Botany, 2022)
Indigenous plant naming systems and systematic botanical nomenclature involve different methodologies that result in different knowledge systems. Botanical nomenclature provides a single, universal name for a plant based on its taxonomic and evolutionary relationships. Indigenous classifications allow ready identification of plants for particular communities sharing a common language and cultural milieu to which the names are specific. The two systems are independent, but they can profit from mutual comparison, and each should be respected and valued for its distinctive role. A recent proposal argues that indigenous vernacular plant names, being older than those given in colonial circumstances, should have priority over existing botanical names. This suggestion, along with the call for greater use of indigenous languages in specific epithets, is here discussed in relation to the New Zealand flora. We conclude that the proposal would require extensive, complex changes to the International Code of Nomenclature, result in nomenclatural instability, and subject indigenous names to the rules of botanical nomenclature while severing them from their local cultural contexts. We suggest the proposal undermines indigenous naming systems, threatens the integrity of indigenous languages, and would disrupt botanical nomenclature for little benefit.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

A New Insight Into Amicula, a Genus of Tiny Marine Benthic Diatoms With the Description of Two New Tropical Species and the Largest Mitogenome Known for a Stramenopile - Romain Gastineau; Chunlian Li; Matt P. Ashworth; Andrzej Witkowski; Monique Turmel; Ewa Górecka; Thomas A. Frankovich; Anna Wachnicka; Christopher S. Lobban; Edward C. Theriot; Christian Otis; Przemysław Dąbek; et al. (Frontiers in Marine Science, 2022)
The current article focuses on the morphological and molecular characterization of the often inconspicuous genus Amicula. This recently erected genus from brackish and marine sediments was monotypic but here we describe two new tropical species: Amicula micronesica sp. nov. and Amicula vermiculata sp. nov. Once considered an incertae sedis genus regarding its higher rank taxonomy, its position among the family Diploneidaceae is proposed here by molecular phylogenetics. The complete plastid and mitochondrial genomes of Amicula micronesica sp. nov. are also presented here. It appears that the 177614-bp long mitogenome is the biggest yet recorded among stramenopiles, due to its invasion by 57 introns. Moreover, it utilizes the genetic code 4 for translation instead of the code 1 usually found among diatoms.

Once-daily feeding is associated with better health in companion dogs: results from the Dog Aging Project - Emily E. Bray; Zihan Zheng; M. Katherine Tolbert; Brianah M. McCoy; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; Matthew D. Dunbar; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The acute effects of action observation on muscle strength/weakness and corticospinal excitability in older adults - Kylie K. Harmon; Ryan M. Girts; Jason I. Pagan; Gabriela Rodriguez; Matt S. Stock (Experimental Brain Research, 2022)

Throughfall Deposition Chemistry in the Great Smoky Mountains National Park: Landscape and Seasonal Effects - John S. Schwartz; Andrew Veeneman; Matt A. Kulp; James R. Renfro (Water, Air, & Soil Pollution, 2022)

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

Watershed-scale Land Use Change Increases Ecosystem Metabolism in an Agricultural Stream - Matt T. Trentman; Jennifer L. Tank; Robert T. Davis; Brittany R. Hanrahan; Ursula H. Mahl; Sarah S. Roley (Ecosystems, 2022)

Genetic variation reveals broad‐scale biogeographic patterns and challenges species’ classification in the Kunzea ericoides (kānuka; Myrtaceae) complex from New Zealand - Peter B. Heenan; Matt S. McGlone; Caroline M. Mitchell; Dagmar F. Cheeseman; Gary J. Houliston (New Zealand Journal of Botany, 2022)
Kunzea (kānuka) in New Zealand comprises ten endemic species following a recent taxonomic revision, several of which are abundant, widespread and ecologically important as early successional colonisers. The species are difficult to recognise in the field in many areas, some plants appear intermediate between species and it has been argued hybrids are common. Microsatellite markers are used to investigate genetic variation in these ten species. The species are only weakly supported as they are characterised by low differentiation as reported by F ST and high allele migration (Nm). F ST varied between 0.027 ( K. robusta ) and 0.084 ( K. triregensis ). The allopatric K. triregensis and K. salterae had the highest difference in pairwise F ST at 0.155 and the sympatric K. robusta and K. serotina the lowest at 0.005. Allele pairwise net migration (Nm) varied between 1.36 ( K. triregensis and K. salterae ) and 45.24 ( K. robusta and K. serotina ). The two most widespread species, K. robusta and K. serotina , are genetically indistinguishable and share northern and southern genotypic clusters. Six species or groups of species are recognised in the Structure analysis but these too are characterised by low F ST and high allele migration (Nm). Four genotypic clusters shown by Structure analysis are distributed along a north to south latitudinal gradient cutting across species boundaries and corresponding with established biogeographic regions of New Zealand. This provides the strongest pattern of genotypic variation in the study. The weak level of genetic support for the ten Kunzea species, lack of breeding barriers between them, and problems in recognising some of the species in the field, raises questions as to their validity. However, given the ecological, conservation and economic importance of Kunzea , the ten species currently circumscribed should be retained until decisions are made as to how to recognise the variation within the species complex.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Mechanisms underlying lack of functional compensation by insect grazers after tadpole declines in a Neotropical stream - Thomas R. Barnum; John Timothy Wootton; Rebecca J. Bixby; John M. Drake; David Murray‐Stoker; Checo Colón‐Gaud; Amanda T. Rugenski; Therese C. Frauendorf; Scott Connelly; Susan S. Kilham; Matt R. Whiles; Karen R. Lips; et al. (Limnology and Oceanography, 2022)
Resilience of ecosystems to the sudden decline of large‐bodied species is dependent on characteristics of surviving guild members. However, that response may also be mediated by local habitat conditions. Here, we examine the mechanisms behind the observed lack of functional compensation in the algal‐grazing guild by insect grazers following the decline of tadpole grazers in a forested Panamanian stream. We examined: (1) shifts to the individual size distribution of insect grazers between pre‐ and post‐tadpole declines in pool and riffle habitats; (2) tadpole and insect preferences for small‐, medium‐, and large‐sized diatoms; and (3) a causal explanation for why insects did not functionally compensate for tadpole declines. The size distribution of insect grazers following tadpole declines differed between habitats, becoming uniform in pools and more right skewed toward a smaller size class in riffles. In both habitats, tadpoles selectively consumed medium‐sized diatoms but avoided the largest‐sized diatoms. In contrast, grazing insects selectively consumed small‐sized diatoms, but switched to medium‐sized diatoms after tadpole declines. Tadpole declines led to the loss of the strongest interactions between consumers and diatoms. Smaller‐bodied grazing insects could not duplicate these interactions, even with a shift in resource use, providing an explanation for the lack of functional compensation. Furthermore, tadpole declines led to different community structures in each habitat indicating that local habitat conditions mediated the response of surviving guild members. This suggests that the sudden decline of a large‐bodied species does not lead to a singular outcome for the surviving community.

Understanding societal approval of the fishing industry and the influence of third‐party sustainability certification - Lucy M. Robinson; Ingrid van Putten; Blake S. Cavve; Catherine Longo; Matt Watson; Lynda Bellchambers; Emily Fisher; Fabio Boschetti (Fish and Fisheries, 2021)
Commercial fisheries are increasingly interested in greater social acceptance of their operations and practices. For harvesters, achieving acceptance is complex because expectations arise from many societal groups who can differ greatly in their perceptions. Historically, third‐party certification programmes assisted industry in gaining market acceptance (from consumer and investor groups) by improving the ecological sustainability of fishing practices. This focus is diversifying as societal expectations expand beyond ecological concerns to encompass, for instance, equal access and fair distribution of benefits as well as fisheries management and ethical aspects. In this study, we draw on theoretical work from the social acceptance and social licence literature to create a conceptual model that includes eight variables, representing different aspects of societal approval of fisheries. We applied this model to examine the influence of third‐party certification on societal approval of fisheries in Western Australia (WA). Based on study respondents' perceptions, third‐party certification had a statistically significant influence on facilitating government and regulatory approval of industry. Most respondents perceived certification to facilitate industry acceptance from stakeholders, but this was less so for the local community and general public. Contrary to expectations, but perhaps specific to WA because seafood is mostly sold without the ecolabel, certification was less influential on domestic and export market acceptance. Our findings, in WA, highlight certification was not equally influential on all societal approval aspects. Additionally, the conceptual model is sufficiently flexible to assist other fisheries (and industries) in understanding the influence of certification (and other factors) on different societal approval aspects.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

University of Washington Nathan Shock Center: innovation to advance aging research - Matt Kaeberlein; Alessandro Bitto; Maitreya J. Dunham; Warren Ladiges; Su-In Lee; Michael J. MacCoss; Alexander Mendenhall; Daniel E. L. Promislow; Peter S. Rabinovitch; Judit Villén; Lu Wang; Yuliang Wang; et al. (GeroScience, 2021)

Measuring auditory cortical responses in Tursiops truncatus - Matt D. Schalles; Dorian S. Houser; James J. Finneran; Peter Tyack; Barbara Shinn-Cunningham; Jason Mulsow (Journal of Comparative Physiology A, 2021)
Auditory neuroscience in dolphins has largely focused on auditory brainstem responses; however, such measures reveal little about the cognitive processes dolphins employ during echolocation and acoustic communication. The few previous studies of mid- and long-latency auditory-evoked potentials (AEPs) in dolphins report different latencies, polarities, and magnitudes. These inconsistencies may be due to any number of differences in methodology, but these studies do not make it clear which methodological differences may account for the disparities. The present study evaluates how electrode placement and pre-processing methods affect mid- and long-latency AEPs in ( Tursiops truncatus ). AEPs were measured when reference electrodes were placed on the skin surface over the forehead, the external auditory meatus, or the dorsal surface anterior to the dorsal fin. Data were pre-processed with or without a digital 50-Hz low-pass filter, and the use of independent component analysis to isolate signal components related to neural processes from other signals. Results suggest that a meatus reference electrode provides the highest quality AEP signals for analyses in sensor space, whereas a dorsal reference yielded nominal improvements in component space. These results provide guidance for measuring cortical AEPs in dolphins, supporting future studies of their cognitive auditory processing.

Te reo Māori and botanical nomenclature as complementary naming systems for New Zealand's flora - Peter B. Heenan; Matt S. McGlone; Aaron D. Wilton (New Zealand Journal of Botany, 2021)
It is argued that the greater use of te reo Māori and ta re Moriori languages for naming new taxa in the flora of Aotearoa / New Zealand supports the aspirations of Māori and Te Tiriti o Waitangi. However, using these indigenous languages in botanical nomenclature is more complex than a simplistic ‘more is better’, and we identify a number of issues requiring consideration. We appraise Waitangi Tribunal claim Wai 262 and Te Tiriti o Waitangi, collaboration at the interface of mātauranga Māori and research science, debate whether iwi are active collaborators or informants, and, crucially, defend the credibility and utility of te reo Māori / ta re Moriori and botanical nomenclatural systems. We conclude that (1) formal botanical nomenclature and (2) te reo and ta re vernacular plant names are independent, complementary, and mutually supportive classifications, each with different purposes and denoting two functional knowledge systems. Our recommendation when naming new taxa is to derive names from botanical Latin terminology. To provide clarity for the application of indigenous languages in naming Aotearoa / New Zealand vascular plants and bryophytes, an assessment of the rules and recommendations in the International Code of Nomenclature (ICN) is presented, including the use of geographical, personal and plant vernacular names as epithets, diacritical signs, hyphens, combinations of different languages, and epithet authorship. For those considering using te reo or ta re names for a new taxon, we present guidelines that address dialogue between scientists and iwi, key aspects of the ICN to consider, and suggestions for maintaining the scientific credibility of nomenclatural practices. A knowledge gap is identified for ethnobotanical folk taxonomy research into vernacular te reo and ta re names, and to document and promote this mātauranga we recommend Māori‐led research into etymology, hierarchical structure, cultural relationships, whakapapa, and relationships to botanical names.

Exploring controls of the early and stepped deglaciation on the western margin of the British Irish Ice Sheet - Sara Benetti; Richard C. Chiverrell; Colm Ó Cofaigh; Matt Burke; Alicia Medialdea; David Small; Colin Ballantyne; Mark D. Bateman; S. Louise Callard; Peter Wilson; Derek Fabel; Chris D. Clark; et al. (Journal of Quaternary Science, 2021)
New optically stimulated luminescence dating and Bayesian models integrating all legacy and BRITICE‐CHRONO geochronology facilitated exploration of the controls on the deglaciation of two former sectors of the British–Irish Ice Sheet, the Donegal Bay (DBIS) and Malin Sea ice‐streams (MSIS). Shelf‐edge glaciation occurred ~27 ka, before the global Last Glacial Maximum, and shelf‐wide retreat began 26–26.5 ka at a rate of ~18.7–20.7 m a –1 . MSIS grounding zone wedges and DBIS recessional moraines show episodic retreat punctuated by prolonged still‐stands. By ~23–22 ka the outer shelf (~25 000 km 2 ) was free of grounded ice. After this time, MSIS retreat was faster (~20 m a –1 vs. ~2–6 m a –1 of DBIS). Separation of Irish and Scottish ice sources occurred ~20–19.5 ka, leaving an autonomous Donegal ice dome. Inner Malin shelf deglaciation followed the submarine troughs reaching the Hebridean coast ~19 ka. DBIS retreat formed the extensive complex of moraines in outer Donegal Bay at 20.5–19 ka. DBIS retreated on land by ~17–16 ka. Isolated ice caps in Scotland and Ireland persisted until ~14.5 ka. Early retreat of this marine‐terminating margin is best explained by local ice loading increasing water depths and promoting calving ice losses rather than by changes in global temperatures. Topographical controls governed the differences between the ice‐stream retreat from mid‐shelf to the coast.

Modeling affective and cognitive responses to soft-target terrorism over time - Matt Baucum; Richard S. John; William Burns; Kent E. Portney; Jeryl L. Mumpower (Environment Systems and Decisions, 2021)

Lineage through time analyses have their limitations: the case of the New Zealand flora - James K. McCarthy; Matt S. McGlone; Peter B. Heenan (New Zealand Journal of Botany, 2021)
Lineage through time plots (LTTs) are often used to explore past patterns of lineage diversification and community assembly. However, as they are based solely on extant species their ability to accurately depict past events can be questioned. Here, simulation models based on neutral processes are used to explore immigration and extinction scenarios to assist with interpretation of LTT plots generated from molecular clock age estimates for a nearly complete set of extant New Zealand vascular plant genera. With significant genus turnover, model simulations yield smooth exponential and linear semi‐log LTT plots. Abrupt changes in extinction and immigration rates imposed in the scenarios caused only slight alterations of the curves. The vast majority of New Zealand vascular plant genera derive from trans‐oceanic dispersal, and LTT plots generated from divergence dates and fossil data indicate consistently high turnover. Even major geological and climatic events leave minor signatures on LTT plots. Most notably, the maximum Oligocene Marine Transgression (27–22 Ma), when at least 85% of the current landmass was inundated, isn't clearly registered. By themselves, LTT plots shed little light on the biotic effects of climatic or geomorphic change in the remote past and need to be interpreted in the light of fossil and geological data.

Musclesense: a Trained, Artificial Neural Network for the Anatomical Segmentation of Lower Limb Magnetic Resonance Images in Neuromuscular Diseases - Baris Kanber; Jasper M Morrow; Uros Klickovic; Stephen Wastling; Sachit Shah; Pietro Fratta; Amy R McDowell; Matt G Hall; Chris A Clark; Francesco Muntoni; Mary M Reilly; Michael G Hanna; et al. (Neuroinformatics, 2021)

Motor unit action potential amplitude during low torque fatiguing contractions versus high torque non-fatiguing contractions: a multilevel analysis - Kylie K. Harmon; Adam S. Hamilton; Brent D. Johnson; Frank J. Bartek; Ryan M. Girts; Rob J. MacLennan; Debbie L. Hahs-Vaughn; Matt S. Stock (European Journal of Applied Physiology, 2021)

Export of photolabile and photoprimable dissolved organic carbon from the Connecticut River - Byungman Yoon; Jacob D. Hosen; Ethan D. Kyzivat; Jennifer H. Fair; Lisa C. Weber; Kelly S. Aho; Rachel Lowenthal; Serena Matt; William V. Sobczak; Jamie B. Shanley; Jon Morrison; James E. Saiers; et al. (Aquatic Sciences, 2021)

Source Switching Maintains Dissolved Organic Matter Chemostasis Across Discharge Levels in a Large Temperate River Network - J. D. Hosen; K. S. Aho; J. H. Fair; E. D. Kyzivat; S. Matt; J. Morrison; A. Stubbins; L. C. Weber; B. Yoon; P. A. Raymond (Ecosystems, 2021)

Echo intensity as an indicator of skeletal muscle quality: applications, methodology, and future directions - Matt S. Stock; Brennan J. Thompson (European Journal of Applied Physiology, 2021)

Beyond species counts for assessing, valuing, and conserving biodiversity: response to Wallach et al. 2019 - Ninon F. V. Meyer; Niko Balkenhol; Trishna Dutta; Maarten Hofman; Jean‐Yves Meyer; Euan G. Ritchie; Charlotte Alley; Chad Beranek; Cassandra K. Bugir; Alex Callen; Simon Clulow; Michael V. Cove; et al. (Conservation Biology, 2021)
Article impact statement : Combining native and non‐native species to evaluate biodiversity is overly simplistic and may undermine the conservation of ecosystems.

Supposed snake specialist consumes monitor lizards: diet and trophic implications of king cobra feeding ecology - Max D. Jones; Matt S. Crane; Inês M. S. Silva; Taksin Artchawakom; Surachit Waengsothorn; Pongthep Suwanwaree; Colin T. Strine; Matt Goode (Ecology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Human‐mediated dispersal and disturbance shape the metapopulation dynamics of a long‐lived herb - James M. Bullock; Matthias C. Wichmann; Rosemary S. Hails; David J. Hodgson; Matt J. Alexander; Kathryn Morley; Tatjana Knopp; Lucy E. Ridding; Danny A. P. Hooftman (Ecology, 2020)
As anthropogenic impacts on the natural world escalate, there is increasing interest in the role of humans in dispersing seeds. But the consequences of this Human‐Mediated Dispersal (HMD) on plant spatial dynamics are little studied. In this paper, we ask how secondary dispersal by HMD affects the dynamics of a natural plant metapopulation. In addition to dispersal between patches, we suggest within‐patch processes can be critical. To address this, we assess how variation in local population dynamics, caused by small‐scale disturbances, affects metapopulation size. We created an empirically based model with stochastic population dynamics and dispersal among patches, which represented a real‐world, cliff‐top metapopulation of wild cabbage Brassica oleracea . We collected demographic data from multiple populations by tagging plants over eight years. We assessed seed survival, and establishment and survival of seedlings in intact vegetation vs. small disturbances. We modeled primary dispersal by wind using field data and used experimental data on secondary HMD by hikers. We monitored occupancy patterns over a 14‐yr period in the real metapopulation. Disturbance had large effects on local population growth rates, by increasing seedling establishment and survival. This meant that the modeled metapopulation grew in size only when the area disturbed in each patch was above 35%. In these growing metapopulations, although only 0.2% of seeds underwent HMD, this greatly enhanced metapopulation growth rates. Similarly, HMD allowed more colonizations in declining metapopulations under low disturbance, and this slowed the rate of decline. The real metapopulation showed patterns of varying patch occupancy over the survey years, which were related to habitat quality, but also positively to human activity along the cliffs, hinting at beneficial effects of humans. These findings illustrate that realistic changes to dispersal or demography, specifically by humans, can have fundamental effects on the viability of a species at the landscape scale.

Outmigration survival of wild Chinook salmon smolts through the Sacramento River during historic drought and high water conditions - Jeremy J. Notch; Alex S. McHuron; Cyril J. Michel; Flora Cordoleani; Matt Johnson; Mark J. Henderson; Arnold J. Ammann (Environmental Biology of Fishes, 2020)
Populations of wild spring-run Chinook salmon in California’s Central Valley, once numbering in the millions, have dramatically declined to record low numbers. Dam construction, habitat degradation, and altered flow regimes have all contributed to depress populations, which currently persist in only a few tributaries to the Sacramento River. Mill Creek (Tehama County) continues to support these threatened fish, and contains some of the most pristine spawning and rearing habitat available in the Central Valley. Despite this pristine habitat, the number of Chinook salmon returning to spawn has declined to record low numbers, likely due to poor outmigration survival rates. From 2013 to 2017, 334 smolts were captured and acoustic tagged while out-migrating from Mill Creek, allowing for movement and survival rates to be tracked over 250 km through the Sacramento River. During this study California experienced both a historic drought and record rainfall, resulting in dramatic fluctuations in year-to-year river flow and water temperature. Cumulative survival of tagged smolts from Mill Creek through the Sacramento River was 9.5% (±1.6) during the study, with relatively low survival during historic drought conditions in 2015 (4.9% ± 1.6) followed by increased survival during high flows in 2017 (42.3% ± 9.1). Survival in Mill Creek and the Sacramento River was modeled over a range of flow values, which indicated that higher flows in each region result in increased survival rates. Survival estimates gathered in this study can help focus management and restoration actions over a relatively long migration corridor to specific regions of low survival, and provide guidance for management actions in the Sacramento River aimed at restoring populations of threatened Central Valley spring-run Chinook salmon.

Where Is Dopamine and how do Immune Cells See it?: Dopamine-Mediated Immune Cell Function in Health and Disease - S. M. Matt; P. J. Gaskill (Journal of Neuroimmune Pharmacology, 2020)

Contribution of Seagrass Blue Carbon Toward Carbon Neutral Policies in a Touristic and Environmentally-Friendly Island - Camila Bedulli; Paul S. Lavery; Matt Harvey; Carlos M. Duarte; Oscar Serrano (Frontiers in Marine Science, 2020)

Compound heterozygous mutations in SNAP29 is associated with Pelizaeus-Merzbacher-like disorder (PMLD) - Lorida Llaci; Keri Ramsey; Newell Belnap; Ana M. Claasen; Chris D. Balak; Szabolcs Szelinger; Wayne M. Jepsen; Ashley L. Siniard; Ryan Richholt; Tyler Izat; Marcus Naymik; Matt De Both; et al. (Human Genetics, 2019)

Cenozoic formation and colonisation history of the New Zealand vascular flora based on molecular clock dating of the plastid rbcL gene - Peter B. Heenan; Matt S. McGlone (New Zealand Journal of Botany, 2019)
A colonisation history for 411 extant genera and 477 lineages of the vascular flora of New Zealand was constructed using the plastid rbcL gene. Molecular clock crown ages suggest that the Eocene‐Oligocene transition extinction at 33.9 Ma was critical to the development of the extant flora as few lineages, mostly ferns and conifers, predate this event. Based on crown dates, almost all extant angiosperm lineages have established after the Eocene‐Oligocene transition extinction. The Oligocene marine transgression had little discernible impact on the formation of the extant flora, as at the culmination of the inundation (22.0–25.0 Ma) fifty extant lineages of vascular plant were present and another eight lineages originated during this time. The majority of extant species (89%) originated after the end of the Miocene Thermal Optimum at about 15.0 Ma. Nearly 50% of the extant species have evolved during mountain uplift and glaciation of the late Pliocene‐Pleistocene (0–4.99 Ma). Therefore, despite a residual contribution from the Eocene, Oligocene and early to mid Miocene periods, the New Zealand vascular flora essentially originated in the late Miocene and after.

Age-Related Differences in the Predictability of Fast Gait Speed with Absolute and Rapid Squat Strength - Matt S. Stock; Brennan J. Thompson; Eric J. Sobolewski (Journal of Science in Sport and Exercise, 2019)

Improving sensitivity, specificity, and reproducibility of individual brainstem activation - Eva Matt; Florian Ph. S. Fischmeister; Ahmad Amini; Simon D. Robinson; Alexandra Weber; Thomas Foki; Elke R. Gizewski; Roland Beisteiner (Brain Structure and Function, 2019)

No acute effects of placebo or open-label placebo treatments on strength, voluntary activation, and neuromuscular fatigue - Alina P. Swafford; Dennis P. Kwon; Rob J. MacLennan; David H. Fukuda; Jeffrey R. Stout; Matt S. Stock (European Journal of Applied Physiology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Enhancement of primary production during drought in a temperate watershed is greater in larger rivers than headwater streams - J. D. Hosen; K. S. Aho; A. P. Appling; E. C. Creech; J. H. Fair; R. O. Hall; E. D. Kyzivat; R. S. Lowenthal; S. Matt; J. Morrison; J. E. Saiers; J. B. Shanley; et al. (Limnology and Oceanography, 2019)
Drought is common in rivers, yet how this disturbance regulates metabolic activity across network scales is largely unknown. Drought often lowers gross primary production (GPP) and ecosystem respiration (ER) in small headwaters but by contrast can enhance GPP and cause algal blooms in downstream estuaries. We estimated ecosystem metabolism across a nested network of 13 reaches from headwaters to the main stem of the Connecticut River from 2015 through 2017, which encompassed a pronounced drought. During drought, GPP and ER increased, but with greater enhancement in larger rivers. Responses of GPP and ER were partially due to warmer temperatures associated with drought, particularly in the larger rivers where temperatures during summer drought were > 10°C higher than typical summer baseflow. The larger rivers also had low canopy cover, which allowed primary producers to take advantage of lower turbidity and fewer cloudy days during drought. We conclude that GPP is enhanced by higher temperature, lower turbidity, and longer water residence times that are all a function of low discharge, but ecosystem response in temperate watersheds to these drivers depends on light availability regulated by riparian canopy cover. In larger rivers, GPP increased more than ER during drought, even leading to temporary autotrophy, an otherwise rare event in the typically light‐limited heterotrophic Connecticut River main stem. With climate change, rivers and streams may become warmer and drought frequency and severity may increase. Such changes may increase autotrophy in rivers with broad implications for carbon cycling and water quality in aquatic ecosystems.

The time course of cross-education during short-term isometric strength training - Joshua C. Carr; Xin Ye; Matt S. Stock; Michael G. Bemben; Jason M. DeFreitas (European Journal of Applied Physiology, 2019)

The relationship of cerebral microbleeds to cognition and incident dementia in non-demented older individuals - Matt Paradise; Adam Seruga; John D. Crawford; Joga Chaganti; Anbupalam Thalamuthu; Nicole A. Kochan; Henry Brodaty; Wei Wen; Perminder S. Sachdev (Brain Imaging and Behavior, 2019)

Persistence through tough times: fixed and shifting refuges in threatened species conservation - April E. Reside; Natalie J. Briscoe; Chris R. Dickman; Aaron C. Greenville; Bronwyn A. Hradsky; Salit Kark; Michael R. Kearney; Alex S. Kutt; Dale G. Nimmo; Chris R. Pavey; John L. Read; Euan G. Ritchie; et al. (Biodiversity and Conservation, 2019)

Corrigendum: Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2019)

C 4 anatomy can evolve via a single developmental change - Marjorie R. Lundgren; Luke T. Dunning; Jill K. Olofsson; Jose J. Moreno‐Villena; Jacques W. Bouvier; Tammy L. Sage; Roxana Khoshravesh; Stefanie Sultmanis; Matt Stata; Brad S. Ripley; Maria S. Vorontsova; Guillaume Besnard; et al. (Ecology Letters, 2019)
C 4 photosynthesis is a complex trait that boosts productivity in warm environments. Paradoxically, it evolved independently in numerous plant lineages, despite requiring specialised leaf anatomy. The anatomical modifications underlying C 4 evolution have previously been evaluated through interspecific comparisons, which capture numerous changes besides those needed for C 4 functionality. Here, we quantify the anatomical changes accompanying the transition between non‐C 4 and C 4 phenotypes by sampling widely across the continuum of leaf anatomical traits in the grass Alloteropsis semialata . Within this species, the only trait that is shared among and specific to C 4 individuals is an increase in vein density, driven specifically by minor vein development that yields multiple secondary effects facilitating C 4 function. For species with the necessary anatomical preconditions, developmental proliferation of veins can therefore be sufficient to produce a functional C 4 leaf anatomy, creating an evolutionary entry point to complex C 4 syndromes that can become more specialised.

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Variation in Detrital Resource Stoichiometry Signals Differential Carbon to Nutrient Limitation for Stream Consumers Across Biomes - Kaitlin J. Farrell; Amy D. Rosemond; John S. Kominoski; Sophia M. Bonjour; Janine Rüegg; Lauren E. Koenig; Christina L. Baker; Matt T. Trentman; Tamara K. Harms; William H. McDowell (Ecosystems, 2018)

Whole‐river manipulation of olfactory cues affects upstream migration of sockeye salmon - S. Matthew Drenner; William L. Harrower; Matt T. Casselman; Nolan N. Bett; Aurthor L. Bass; Collin T. Middleton; Scott G. Hinch (Fisheries Management and Ecology, 2018)
This study experimentally manipulated olfactory cues in a river by adjusting hydropower operation and monitored behavioural responses of 193 adult sockeye salmon, Oncorhynchus nerka (Walbaum), using radio telemetry. Experimental dilution of olfactory cues in a tributary to 72% natal water relative to non‐natal water was associated with 80% reduced odds of fish entering the tributary from a river mainstem and increased migration times by an average of 12.2 hr, with females taking 4.6 hr longer than males to enter the tributary. Additionally, males delayed 2.7 hr longer than females at a diversion outlet in the river mainstem that discharged a natal water source during experimentally diluted olfactory conditions. Increased migration time associated with dilute olfactory cues would decrease energy available for reproduction and potentially reduce fitness. Hydropower managers should continue to regulate natal water conditions in the Seton River during sockeye salmon migrations to avoid negative impacts on migration timing and success.

Intra-specific variation in skull morphology of juvenile Chelonia mydas in the southwestern Atlantic Ocean - Valéria F. Coelho; Camila Domit; Matt K. Broadhurst; Laura Prosdocimi; Hideaki Nishizawa; Fernanda S. Almeida (Marine Biology, 2018)

Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2018)
Aim We analysed a dataset composed of multiple palaeoclimate and lake‐sediment pollen records from New England to explore how postglacial changes in the composition and spatial patterns of vegetation were controlled by regional‐scale climate change, a subregional environmental gradient, and landscape‐scale variations in soil characteristics. Location The 120,000‐km 2 study area includes parts of Vermont and New Hampshire in the north, where sites are 150–200 km from the Atlantic Ocean, and spans the coastline from southeastern New York to Cape Cod and the adjacent islands, including Block Island, the Elizabeth Islands, Nantucket, and Martha's Vineyard. Methods We analysed pollen records from 29 study sites, using multivariate cluster analysis to visualize changes in the composition and spatial patterns of vegetation during the last 14,000 years. The pollen data were compared with temperature and precipitation reconstructions. Results Boreal forest featuring Picea and Pinus banksiana was present across the region when conditions were cool and dry 14,000–12,000 calibrated 14 C years before present (ybp). Pinus strobus became regionally dominant as temperatures increased between 12,000 and 10,000 ybp. The composition of forests in inland and coastal areas diverged in response to further warming after 10,000 ybp, when Quercus and Pinus rigida expanded across southern New England, whereas conditions remained cool enough in inland areas to maintain Pinus strobus . Increasing precipitation allowed Tsuga canadensis , Fagus grandifolia , and Betula to replace Pinus strobus in inland areas during 9,000–8,000 ybp, and also led to the expansion of Carya across the coastal part of the region beginning at 7,000–6,000 ybp. Abrupt cooling at 5,500–5,000 ybp caused sharp declines in Tsuga in inland areas and Quercus at some coastal sites, and the populations of those taxa remained low until they recovered around 3,000 ybp in response to rising precipitation. Throughout most of the Holocene, sites underlain by sandy glacial deposits were occupied by Pinus rigida and Quercus . Main conclusions Postglacial changes in the composition and spatial pattern of New England forests were controlled by long‐term trends and abrupt shifts in temperature and precipitation, as well as by the environmental gradient between coastal and inland parts of the region. Substrate and soil moisture shaped landscape‐scale variations in forest composition.

Climate change projections for the surface ocean around New Zealand - Cliff S. Law; Graham J. Rickard; Sara E. Mikaloff‐Fletcher; Matt H. Pinkerton; Erik Behrens; Steve M. Chiswell; Kim Currie (New Zealand Journal of Marine and Freshwater Research, 2018)
The future status of the surface ocean around New Zealand was projected using two Earth System Models and four emission scenarios. By 2100 mean changes are largest under Representative Concentration Pathway 8.5 (RCP8.5), with a +2.5°C increase in sea surface temperature, and decreases in surface mixed layer depth (15%), macronutrients (7.5–20%), primary production (4.5%) and particle flux (12%). Largest macronutrient declines occur in the eastern Chatham Rise and subantarctic waters to the south, whereas dissolved iron increases in subtropical waters. Surface pH projections, validated against subantarctic time‐series data, indicate a 0.335 decline to ∼7.77 by 2100. However, projected pH is sensitive to future CO 2 emissions, remaining within the current range under RCP2.6, but decreasing below it by 2040 with all other scenarios. Sub‐regions vulnerable to climate change include the Chatham Rise, polar waters south of 50°S, and subtropical waters north of New Zealand, whereas the central Tasman Sea is least affected.

Systemic Edwardsiella tarda infection in a Western African lungfish ( Protopterus annectens ) with cytologic observation of heterophil projections - Estelle Rousselet; Nicole I. Stacy; David S. Rotstein; Tom B. Waltzek; Matt J. Griffin; Ruth Francis‐Floyd (Journal of Fish Diseases, 2018)
This report describes a case of systemic bacterial infection caused by Edwardsiella tarda in a Western African lungfish ( Protopterus annectens ) exposed to poor environmental and husbandry conditions. The fish presented with a large, external ulcerative lesion and died 2 weeks after developing anorexia. Histological evaluation revealed multifocal areas of necrosis and heterophilic and histiocytic inflammation throughout multiple tissues. Gram stain identified small numbers of intra‐ and extracellular monomorphic Gram‐negative 1 to 2 μm rod‐shaped bacilli. Cytology of lung granuloma, kidney and testes imprints identified heterophilic inflammation with phagocytosis of small monomorphic bacilli and some heterophils exhibiting cytoplasmic projections indicative of heterophil extracellular traps (HETs). Initial phenotypic analysis of isolates from coelomic fluid cultures identified E. tarda . Subsequent molecular analysis of spleen, liver and intestine DNA using an E . tarda ‐specific endpoint PCR assay targeting the bacterial fimbrial subunit yielded a 115 bp band. Sequencing and BLASTN search revealed the sequence was identical (76/76) to E . tarda strain FL 95‐01 (GenBank acc. CP011359 ) and displayed 93% sequence identity (66/71) to Edwardsiella hoshinae strain ATCC 35051 (GenBank acc. CP011359 ). This is the first report of systemic edwardsiellosis in a lungfish with concurrent cytologically identified structures suggestive of HETs.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

A call to action for climate change research on Caribbean dry forests - Howard P. Nelson; Eleanor S. Devenish-Nelson; Bonnie L. Rusk; Matt Geary; Andrew J. Lawrence (Regional Environmental Change, 2018)

Distinct Siderophores Contribute to Iron Cycling in the Mesopelagic at Station ALOHA - Randelle M. Bundy; Rene M. Boiteau; Craig McLean; Kendra A. Turk-Kubo; Matt R. McIlvin; Mak A. Saito; Benjamin A. S. Van Mooy; Daniel J. Repeta (Frontiers in Marine Science, 2018)

Geographically distributed hybrid testing & collaboration between geotechnical centrifuge and structures laboratories - Mobin Ojaghi; Ignacio Lamata Martínez; Matt S. Dietz; Martin S. Williams; Anthony Blakeborough; Adam J. Crewe; Colin A. Taylor; S. P. Gopal Madabhushi; Stuart K. Haigh (Earthquake Engineering and Engineering Vibration, 2018)

Role of Re-entry Tears on the Dynamics of Type B Dissection Flap - Saranya Canchi; Xiaomei Guo; Matt Phillips; Zachary Berwick; Jarin Kratzberg; Joshua Krieger; Blayne Roeder; Stephan Haulon; Sean Chambers; Ghassan S. Kassab (Annals of Biomedical Engineering, 2018)

Holy flux: spatial and temporal variation in massive pulses of emerging insect biomass from western U.S. rivers - David M. Walters; Jeff S. Wesner; Robert E. Zuellig; Dan A. Kowalski; Matt C. Kondratieff (Ecology, 2018)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Evaluation of a Ferrozine Based Autonomous in Situ Lab-on-Chip Analyzer for Dissolved Iron Species in Coastal Waters - Felix Geißler; Eric P. Achterberg; Alexander D. Beaton; Mark J. Hopwood; Jennifer S. Clarke; André Mutzberg; Matt C. Mowlem; Douglas P. Connelly (Frontiers in Marine Science, 2017)

The New Zealand endemic Plagiochila caducifolia is a disjunct population of Plagiochila spinulosa (Plagiochilaceae: Jungermanniopsida) - Matt A. M. Renner; Margaret M. Heslewood; Simon D. F. Patzak; Kathrin Feldberg; Alfons Schäfer‐Verwimp; David S. Rycroft; Jochen Heinrichs (New Zealand Journal of Botany, 2017)
We present molecular data demonstrating that the New Zealand endemic Plagiochila caducifolia represents an isolated population of Plagiochila (sect. Arrectae ) spinulosa , a species previously thought confined to the eastern Holarctic but which also occurs in Lesotho, southern Africa. In New Zealand, the wide distribution of P. spinulosa in undisturbed and relatively isolated habitats throughout the South Island is consistent with an indigenous, rather than adventive, species. Plagiochila spinulosa is the first reported bipolar disjunct species within the Plagiochilaceae. Although other bipolar disjunctions are known in vascular and non‐vascular plants, they usually involve species with wider circumboreal or circumarctic distributions, presumably indicating an origin in the Northern Hemisphere. Most species of Plagiochila sect. Arrectae reproduce asexually by caducous leaves and have disjunct distributions; the significance of this correlation and biogeographic patterns in this lineage both require testing against additional data.

Oceanic temperate forest versus warm temperate rainforest: a reply to Grubb et al. (2017) - Matt S. McGlone; Robert Buitenwerf; Sarah J. Richardson (New Zealand Journal of Botany, 2017)

Rapamycin treatment attenuates age-associated periodontitis in mice - Jonathan Y. An; Ellen K. Quarles; Surapat Mekvanich; Alex Kang; Anthony Liu; Danielle Santos; Richard A. Miller; Peter S. Rabinovitch; Timothy C. Cox; Matt Kaeberlein (GeroScience, 2017)

Does inherent flammability of grass and litter fuels contribute to continental patterns of landscape fire activity? - Lynda D. Prior; Brett P. Murphy; Grant J. Williamson; Mark A. Cochrane; W. Matt Jolly; David M. J. S. Bowman (Journal of Biogeography, 2017)
Aims To (1) identify the trade‐offs among flammability attributes within grass and litter fuel types; (2) determine how flammability attributes of grass and litter fuels vary across macro‐ecological gradients; and (3) test our hypothesis that inherent flammability attributes of grass and litter fuels scale to satellite‐derived proxies for fire frequency and intensity. Location Continent of Australia. Methods Samples of litter and grass fuels collected from 133 sites across Australia were oven dried, then burnt under controlled conditions. Measurements of ignitability, combustibility and sustainability were made. Estimates of fire frequency and fire radiative power (a proxy for intensity) were derived from satellite imagery. Multivariate analyses were used to identify inter‐relationships among variables and trends across macro‐ecological gradients. Results Flammability was best described by two axes: high rate of combustion versus long duration of burning, and fast rate of spread versus high maximum temperature. As expected, our study confirmed that grass and litter fuel types have inherently differently flammability attributes whereby grass samples burn more quickly, with a higher rate of spread, than litter samples. However, there were also smaller differences in flammability attributes within fuel types, which scaled to rainfall, temperature and soil phosphorus concentrations. In keeping with our hypothesis, we found correlations between inherent fuel flammability attributes and landscape fire activity across the Australian continent. Fire frequency and rate of combustion of grass fuels were both highest in the tropics, and fire intensity and maximum temperature during combustion of litter fuels were highest in temperate areas. Main conclusions At a continental scale, we found landscape fire activity was correlated with inherent flammability of grass and litter fuels. This inherent flammability contributes to observed pyrogeographical patterns that are shaped by climate through its known effects on plant productivity, the abundance of cured grass biomass and fire weather.

The time course of short-term hypertrophy in the absence of eccentric muscle damage - Matt S. Stock; Jacob A. Mota; Ryan N. DeFranco; Katherine A. Grue; A. Unique Jacobo; Eunhee Chung; Jordan R. Moon; Jason M. DeFreitas; Travis W. Beck (European Journal of Applied Physiology, 2017)

Invasion dynamics of Asian hornet, Vespa velutina (Hymenoptera: Vespidae): a case study of a commune in south-west France - Daniel N. Franklin; Mike A. Brown; Samik Datta; Andrew G. S. Cuthbertson; Giles E. Budge; Matt J. Keeling (Applied Entomology and Zoology, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Validation of Criteria to Guide Prehospital Naloxone Administration for Drug-Related Altered Mental Status - Matt S. Friedman; Alex F. Manini (Journal of Medical Toxicology, 2016)

Biogeography and ecology of south‐temperate forests - Matt S McGlone; Christopher H Lusk; Juan J Armesto (New Zealand Journal of Botany, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Climate change and larval transport in the ocean: fractional effects from physical and physiological factors - Matthew S. Kendall; Matt Poti; Kristopher B. Karnauskas (Global Change Biology, 2016)
Changes in larval import, export, and self‐seeding will affect the resilience of coral reef ecosystems. Climate change will alter the ocean currents that transport larvae and also increase sea surface temperatures ( SST ), hastening development, and shortening larval durations. Here, we use transport simulations to estimate future larval connectivity due to: (1) physical transport of larvae from altered circulation alone, and (2) the combined effects of altered currents plus physiological response to warming. Virtual larvae from islands throughout Micronesia were moved according to present‐day and future ocean circulation models. The Hybrid Coordinate Ocean Model ( HYCOM ) spanning 2004–2012 represented present‐day currents. For future currents, we altered HYCOM using analysis from the National Center for Atmospheric Research Community Earth System Model, version 1‐Biogeochemistry, Representative Concentration Pathway 8.5 experiment. Based on the NCAR model, regional SST is estimated to rise 2.74 °C which corresponds to a ~17% decline in larval duration for some taxa. This reduction was the basis for a separate set of simulations. Results predict an increase in self‐seeding in 100 years such that 62–76% of islands experienced increased self‐seeding, there was an average domainwide increase of ~1–3% points in self‐seeding, and increases of up to 25% points for several individual islands. When changed currents alone were considered, approximately half (i.e., random) of all island pairs experienced decreased connectivity but when reduced PLD was added as an effect, ~65% of connections were weakened. Orientation of archipelagos relative to currents determined the directional bias in connectivity changes. There was no universal relationship between climate change and connectivity applicable to all taxa and settings. Islands that presently export large numbers of larvae but that also maintain or enhance this role into the future should be the focus of conservation measures that promote long‐term resilience of larval supply.

Rapid treatment of vessels fouled with an invasive polychaete, Sabella spallanzanii , using a floating dock and chlorine as a biocide - Donald J. Morrisey; Craig V. Depree; Christopher W. Hickey; Don S. McKenzie; Irene Middleton; Matt D. Smith; Michael Stewart; Karen J. Thompson (Biofouling, 2016)

The findings of Damas et al. have not influenced the previously proposed time course of skeletal muscle hypertrophy - Jason M. DeFreitas; Travis W. Beck; Matt S. Stock (European Journal of Applied Physiology, 2016)

Intensification of Southern Hemisphere westerly winds 2000–1000 years ago: evidence from the subantarctic Campbell and Auckland Islands (52–50°S) - Chris S. M. Turney; Matt M c Glone; Jonathan Palmer; Christopher Fogwill; Alan Hogg; Zoë A. Thomas; Mathew Lipson; Janet M. Wilmshurst; Pavla Fenwick; Richard T. Jones; Ben Hines; Graeme F. Clark (Journal of Quaternary Science, 2016)
The Southern Ocean plays a significant role in driving global climate–ocean–carbon dynamics. Unfortunately, a relative dearth of datasets across the region limits our ability to understand past and future mechanisms of change. Here we report a new dataset from the south‐west Pacific: radiocarbon‐dated subfossil tree stumps ( Dracophyllum ) eroding out from peat exposures on Campbell and Auckland Islands (52–50°S). Dracophyllum are the southernmost growing trees in the south‐west Pacific and their growth on exposed sites and at altitude is strongly controlled by the prevailing westerly airflow, providing a unique measure of past changes in zonal wind strength. Here we demonstrate a significant collapse in the altitudinal limit of growth between approximately 2000 and 1000 years ago (hereafter 2–1 ka), consistent with other records across the Southern Hemisphere that indicate westerly airflow was significantly enhanced. Importantly, this period in the late Holocene was one of marked change across the broader region, suggesting westerly airflow played a key role in driving Southern Ocean variability at this time.

Prior human polyomavirus and papillomavirus infection and incident lung cancer: a nested case–control study - Danny V. Colombara; Lisa E. Manhart; Joseph J. Carter; Stephen E. Hawes; Noel S. Weiss; James P. Hughes; Matt J. Barnett; Gary E. Goodman; Jennifer S. Smith; You-Lin Qiao; Denise A. Galloway (Cancer Causes & Control, 2015)

Aboveground vertebrate and invertebrate herbivore impact on net N mineralization in subalpine grasslands - Anita C. Risch; Martin Schütz; Martijn L. Vandegehuchte; Wim H. van der Putten; Henk Duyts; Ursina Raschein; Dariusz J. Gwiazdowicz; Matt D. Busse; Deborah S. Page-Dumroese; Stephan Zimmermann (Ecology, 2015)
Aboveground herbivores have strong effects on grassland nitrogen (N) cycling. They can accelerate or slow down soil net N mineralization depending on ecosystem productivity and grazing intensity. Yet, most studies only consider either ungulates or invertebrate herbivores, but not the combined effect of several functionally different vertebrate and invertebrate herbivore species or guilds. We assessed how a diverse herbivore community affects net N mineralization in subalpine grasslands. By using size‐selective fences, we progressively excluded large, medium, and small mammals, as well as invertebrates from two vegetation types, and assessed how the exclosure types (ET) affected net N mineralization. The two vegetation types differed in long‐term management (centuries), forage quality, and grazing history and intensity. To gain a more mechanistic understanding of how herbivores affect net N mineralization, we linked mineralization to soil abiotic (temperature; moisture; NO 3 − , NH 4 + , and total inorganic N concentrations/pools; C, N, P concentrations; pH; bulk density), soil biotic (microbial biomass; abundance of collembolans, mites, and nematodes) and plant (shoot and root biomass; consumption; plant C, N, and fiber content; plant N pool) properties. Net N mineralization differed between ET, but not between vegetation types. Thus, short‐term changes in herbivore community composition and, therefore, in grazing intensity had a stronger effect on net N mineralization than long‐term management and grazing history. We found highest N mineralization values when only invertebrates were present, suggesting that mammals had a negative effect on net N mineralization. Of the variables included in our analyses, only mite abundance and aboveground plant biomass explained variation in net N mineralization among ET. Abundances of both mites and leaf‐sucking invertebrates were positively correlated with aboveground plant biomass, and biomass increased with progressive exclusion. The negative impact of mammals on net N mineralization may be related partially to (1) differences in the amount of plant material (litter) returned to the belowground subsystem, which induced a positive bottom‐up effect on mite abundance, and (2) alterations in the amount and/or distribution of dung, urine, and food waste. Thus, our results clearly show that short‐term alterations of the aboveground herbivore community can strongly impact nutrient cycling within ecosystems independent of long‐term management and grazing history.

Developing Critical Loads of Nitrate and Sulfate Deposition to Watersheds of the Great Smoky Mountains National Park, USA - Qingtao Zhou; Charles T. Driscoll; Stephen E. Moore; Matt A. Kulp; James R. Renfro; John S. Schwartz; Meijun Cai; Jason A. Lynch (Water, Air, & Soil Pollution, 2015)

Evidence for the persistence of food web structure after amphibian extirpation in a Neotropical stream - Thomas R. Barnum; John M. Drake; Checo Colón-Gaud; Amanda T. Rugenski; Therese C. Frauendorf; Scott Connelly; Susan S. Kilham; Matt R. Whiles; Karen R. Lips; Catherine M. Pringle (Ecology, 2015)
Species losses are predicted to simplify food web structure, and disease‐driven amphibian declines in Central America offer an opportunity to test this prediction. Assessment of insect community composition, combined with gut content analyses, was used to generate periphyton–insect food webs for a Panamanian stream, both pre‐ and post‐amphibian decline. We then used network analysis to assess the effects of amphibian declines on food web structure. Although 48% of consumer taxa, including many insect taxa, were lost between pre‐ and post‐amphibian decline sampling dates, connectance declined by less than 3%. We then quantified the resilience of food web structure by calculating the number of expected cascading extirpations from the loss of tadpoles. This analysis showed the expected effects of species loss on connectance and linkage density to be more than 60% and 40%, respectively, than were actually observed. Instead, new trophic linkages in the post‐decline food web reorganized the food web topology, changing the identity of “hub” taxa, and consequently reducing the effects of amphibian declines on many food web attributes. Resilience of food web attributes was driven by a combination of changes in consumer diets, particularly those of insect predators, as well as the appearance of generalist insect consumers, suggesting that food web structure is maintained by factors independent of the original trophic linkages.

Mitigating unaccounted fishing mortality from gillnets and traps - Sebastian S Uhlmann; Matt K Broadhurst (Fish and Fisheries, 2015)
Gillnets and traps often are considered to have fewer holistic environmental impacts than active fishing gears. However, in addition to the targeted catches, gillnets and traps still cause unwanted mortalities due to (i) discarding, (ii) ghost fishing of derelict gear, (iii) depredation, (iv) escaping or dropping out of gear, (v) habitat damage, and potentially (vi) avoiding gear and predation and (vii) infection of injuries sustained from most of the above. Population‐level concerns associated with such ‘unaccounted fishing mortalities’ from gillnets and traps have been sufficient to warrant numerous attempts at mitigation. In this article, we reviewed relevant research efforts, locating 130 studies in the primary literature that concomitantly quantified mortalities and their resolution through technical modifications, with the division of effort indicating ongoing concerns. Most studies (85) have focused on discard mortality, followed by ghost‐fishing (24), depredation (10) and escape (8) mortalities. The remaining components have been poorly studied (3). All problematic mortality components are affected by key biological (e.g. species), technical (e.g. fishing mechanisms) and/or environmental (e.g. temperature) factors. We propose that these key factors should be considered as part of a strategy to reduce impacts of these gears by first assessing modifications within and then beyond conventional configurations, followed by changes to operational and handling practices. Justification for this three‐tiered approach is based not only on the potential for cumulative reduction benefits, but also on the likely ease of adoption, legislation and compliance.

Potential impact of invasive alien species on ecosystem services provided by a tropical forested ecosystem: a case study from Montserrat - Kelvin S.-H. Peh; Andrew Balmford; Jennifer C. Birch; Claire Brown; Stuart H. M. Butchart; James Daley; Jeffrey Dawson; Gerard Gray; Francine M. R. Hughes; Stephen Mendes; James Millett; Alison J. Stattersfield; et al. (Biological Invasions, 2015)

Palinurid lobster aquaculture: nutritional progress and considerations for successful larval rearing - David S. Francis; Matt L. Salmon; Matt J. Kenway; Michael R. Hall (Reviews in Aquaculture, 2014)
The closed‐cycle rearing of palinurid lobsters in commercially relevant quantities currently represents one of the most difficult challenges facing modern‐day aquaculture. The length and complexity of the larval life cycle exacerbate the problem, comprising the major bottleneck to their successful aquaculture. The general consensus is that developments in the key research area of nutrition will provide the necessary breakthroughs to make the closed‐cycle rearing of lobster a reality. Due to the cryptic nature of feeding preferences and complex larval morphology, a commercially formulated feed for their culture does currently not exist. Nevertheless, there has been a wealth of research conducted to elucidate many of the unknowns concerning larval nutritional requirements. This review presents a synthesis of this information, ranging from investigations of larval morphology and feeding behaviour, hatchery nutrition practices, the elucidation of wild prey items and the nutritional content of wild‐caught larval species. Based on the information available, this review culminates with a ‘best guess’ formulation for a larval spiny lobster diet, taking aspects concerning both the physical and chemical attributes of formulation into consideration. It is concluded that larval spiny lobsters are likely comparatively low in relation to other larval species with respect to their quantitative dietary requirements. Ultimately, the overall success of the larval cycle appears to be dictated by the stockpiling of lipids to fuel an energy‐demanding metamorphosis and a subsequent nonfeeding puerulus phase. These insights provide valuable direction for the formulation of nutritionally complete feeds to permit the closed‐loop culture of spiny lobster species.

Bark thickness does not explain the different susceptibility of Australian and New Zealand temperate rain forests to anthropogenic fire - Michael J. Lawes; Sarah J. Richardson; Peter J. Clarke; Jeremy J. Midgley; Matt S. McGlone; Peter J. Bellingham (Journal of Biogeography, 2014)
Aim Anthropogenic fires caused New Zealand's temperate rain forests to decline rapidly from 80% to 50% cover after Polynesian arrival. In contrast, Australian temperate rain forests have remained stable in spite of a longer history of fire and human occupation. We evaluate whether New Zealand's conifer‐dominated forests declined because they lack fire resistance traits. We predicted that New Zealand species should have thinner bark than their Australian counterparts, and slower growing conifers should have relatively thicker bark than angiosperms. Location Temperate rain forests of south‐eastern Australia, Tasmania and New Zealand. Methods We examined the ratio of bark thickness to stem diameter (relative bark thickness) as a standardized index (by tree size) of fire resistance. Nonlinear power models were fitted to examine trends in relative bark thickness between trees from New Zealand and Australia. Bark thickness was also compared between species pairs and congeners and by phylogenetically corrected ANOVA. Results Although angiosperms and gymnosperms in New Zealand had thin bark in a global context, they had significantly thicker bark than their Australian counterparts. Bark thickened more rapidly for small trees in New Zealand but declined with increasing stem diameter. Allocation to bark thickness was greater for larger stems in Australia. New Zealand gymnosperms had the thickest bark of all species examined. Main conclusions Fire resistance is a complex syndrome comprising functional traits that ensure protection (resistance – bark) from and recovery (resilience – resprouting) after fire. Thin bark in temperate rain forests suggests weak selection by fire on bark traits. However, the stability of Australian temperate forests in a flammable landscape emphasizes the importance of resprouting, especially basal resprouting, to forest persistence after fire. New Zealand forests do not resprout after fire and lack the fire resistance traits required for recovery from repeated anthropogenic fires.

Southern Hemisphere temperate tree lines are not climatically depressed - Ellen Cieraad; Matt S. McGlone; Brian Huntley (Journal of Biogeography, 2014)
Aim Southern temperate tree lines are found at low elevations compared with their Northern Hemisphere counterparts. They are also regarded as forming at warm temperatures, which has been attributed to taxon‐specific limitations. Using New Zealand tree lines as an example, we assess whether these tree lines are anomalously warm compared with the global mean. Location New Zealand. Methods Soil and air temperatures were measured over 2 years at six New Zealand tree line sites, and compared with other local and global growing season temperature data. In New Zealand and other oceanic regions, the long, variable seasonal transitions make calculations of mean growing season temperatures highly sensitive to how the growing season is defined. We used both the conventional (wide) definition (from when mean weekly root‐zone temperature exceeds 3.2 °C in spring, to when it first falls below 3.2 °C in autumn) and a narrow definition (the period during which temperatures are continuously above 3.2 °C). Application of these criteria leads to similar mean growing season temperatures in continental regions, but different ones in oceanic regions. We tested whether growing season temperatures differ between northern and southern temperate tree lines. Results New Zealand tree lines had a mean root‐zone temperature during the wide growing season of 7.0 °C ± 0.4 SD , not significantly different from those at northern temperate tree lines. The mean temperature of the narrow growing season was 7.8 °C, warmer than tree lines elsewhere, but still within the range reported for temperate tree lines (7–8 °C). Main conclusions Whilst they are found at lower elevations, New Zealand tree lines form at temperatures similar to those at Northern Hemisphere temperate tree lines. Together with similar recent evidence from Chile, these results refute the previously postulated taxon‐specific limitation hypothesis, and suggest these southern temperate tree lines are not climatically depressed, but are governed by the same thermal threshold as other tree lines worldwide.

Fine-scale features on the sea surface in SAR satellite imagery – Part 2: Numerical modeling - S. Matt; A. Fujimura; A. Soloviev; S. H. Rhee; R. Romeiser (Ocean Science, 2014)
With the advent of the new generation of synthetic aperture radar (SAR) satellites, it has become possible to resolve fine-scale features on the sea surface on the scale of meters. The proper identification of sea surface signatures in SAR imagery can be challenging, since some features may be due to atmospheric distortions (gravity waves, squall lines) or anthropogenic influences (slicks), and may not be related to dynamic processes in the upper ocean. In order to improve our understanding of the nature of fine-scale features on the sea surface and their signature in SAR, we have conducted high-resolution numerical simulations combining a three-dimensional non-hydrostatic computational fluid dynamics model with a radar imaging model. The surface velocity field from the hydrodynamic model is used as input to the radar imaging model. The combined approach reproduces the sea surface signatures in SAR of ship wakes, low-density plumes, and internal waves in a stratified environment. The numerical results are consistent with observations reported in a companion paper on in situ measurements during SAR satellite overpasses. Ocean surface and internal waves are also known to produce a measurable signal in the ocean magnetic field. This paper explores the use of computational fluid dynamics to investigate the magnetic signatures of oceanic processes. This potentially provides a link between SAR signatures of transient ocean dynamics and magnetic field fluctuations in the ocean. We suggest that combining SAR imagery with data from ocean magnetometers may be useful as an additional maritime sensing method. The new approach presented in this work can be extended to other dynamic processes in the upper ocean, including fronts and eddies, and can be a valuable tool for the interpretation of SAR images of the ocean surface.

Linkages between grazing history and herbivore exclusion on decomposition rates in mineral soils of subalpine grasslands - Alan G. Haynes; Martin Schütz; Nina Buchmann; Deborah S. Page-Dumroese; Matt D. Busse; Anita C. Risch (Plant and Soil, 2014)

Aquatic Macroinvertebrate Communities and Water Quality at Buffered and Non-Buffered Wetland Sites on Federal Waterfowl Production Areas in the Rainwater Basin, Nebraska - John R. Riens; Matt S. Schwarz; Fatima Mustafa; W. Wyatt Hoback (Wetlands, 2013)

Coiled-coil irregularities of the M1 protein structure promote M1–fibrinogen interaction and influence group A Streptococcus host cell interactions and virulence - Satoshi Uchiyama; Federica Andreoni; Claudia Zürcher; Katrin Schilcher; Miriam Ender; Jerzy Madon; Ulrich Matt; Partho Ghosh; Victor Nizet; Reto A. Schuepbach; Annelies S. Zinkernagel (Journal of Molecular Medicine, 2013)

Agricultural land use alters the seasonality and magnitude of stream metabolism - Natalie A. Griffiths; Jennifer L. Tank; Todd V. Royer; Sarah S. Roley; Emma J. Rosi-Marshall; Matt R. Whiles; Jake J. Beaulieu; Laura T. Johnson (Limnology and Oceanography, 2013)
We present a comprehensive data set of gross primary production (GPP) and ecosystem respiration (ER) in open‐canopy, nutrient‐rich streams draining row‐crop agriculture in the midwestern United States. We used two approaches to characterize temporal and spatial variation in whole‐stream metabolism: continuous measurements in one agricultural stream for 1 yr, and periodic daily measurements in six agricultural streams on six dates spanning summer, autumn, and winter. Continuous measurements revealed high rates of GPP (range: 0.1 to 22.0 g O 2 m −2 d −1 ) and ER (range: −0.9 to −34.8 g O 2 m −2 d −1 ) that varied seasonally with light availability and temperature. GPP and ER were correlated during periods of high autotrophic production, suggesting that autotrophic respiration comprised a large portion of ER; however, the GPP : ER ratio exceeded 1 for only 4% of the year. While there were distinct temporal patterns in metabolism in one agricultural stream, rates of GPP and ER were similar among six streams when assessed via periodic daily measurements, and 26% of all periodic daily measurements were autotrophic with GPP : ER > 1. However, these periodic measurements were collected under baseflow conditions and may have overestimated the extent of autotrophy in agricultural streams. Overall, the open canopy and elevated nutrients of agricultural streams resulted in higher rates of GPP and ER compared with more pristine systems. Estimates of metabolism are needed from underrepresented systems to accurately quantify carbon fluxes from fluvial ecosystems.

Erratum to: Antibodies Against Human BLyS and APRIL Attenuate EAE Development in Marmoset Monkeys - S. Anwar Jagessar; Nicole Heijmans; Luke Oh; Jan Bauer; Erwin L. A. Blezer; Jon D. Laman; Thi-Sau Migone; Matt N. Devalaraja; Bert A. ’t Hart (Journal of Neuroimmune Pharmacology, 2013)

Erratum to: Macronutrient (N, P, K) and Redoximorphic Metal (Fe, Mn) Allocation in Leersia oryzoides (Rice Cutgrass) Grown Under Different Flood Regimes - Samuel C. Pierce; Matt T. Moore; Dan Larsen; S. R. Pezeshki (Water, Air, & Soil Pollution, 2012)

Reconstructing spatial vulnerability to forest loss by fire in pre‐historic New Zealand - George L. W. Perry; Janet M. Wilmshurst; Matt S. McGlone; Aaron Napier (Global Ecology and Biogeography, 2012)
Aim Despite small and transient populations, early Māori transformed large areas of New Zealand's forest landscapes. We sought to isolate the biophysical predictors that explain forest loss in the pre‐historic (i.e. pre‐European) period in New Zealand. Location New Zealand. Methods We used resampled boosted regression trees to isolate the key predictors of forest loss from a suite of 19 topographic, climatic, soil‐related and archaeological predictors at a 1‐km spatial resolution across New Zealand. Results The key predictors of fire‐driven forest loss during New Zealand's pre‐history relate to moisture and elevation gradients, with sites characterized by low moisture levels and gentle slopes being most vulnerable. Proxies for human activity were important in the North Island, where Māori population densities were higher, but not the South Island. The predicted pattern of forest loss and its relationship with biophysical variables suggest that early Māori neither deliberately protected fire‐prone regions nor systematically burnt less fire‐prone ones. Main conclusions Before Māori settlement of New Zealand fire was naturally rare, despite biophysical conditions being conducive to fire spread. The introduction of an ignition source by humans made widespread forest loss inevitable, even in the absence of sustained and deliberate use of fire. Rapid forest loss at the time of human settlement is recurrent across eastern Polynesia, so understanding this dynamic in New Zealand has implications for the region as a whole.

Antibodies Against Human BLyS and APRIL Attenuate EAE Development in Marmoset Monkeys - S. Anwar Jagessar; Nicole Heijmans; Jan Bauer; Erwin L. A. Blezer; Jon D. Laman; Thi-Sau Migone; Matt N. Devalaraja; Bert A. ’t Hart (Journal of Neuroimmune Pharmacology, 2012)

Explaining fire‐driven landscape transformation during the Initial Burning Period of N ew Z ealand's prehistory - George L. W. Perry; Janet M. Wilmshurst; Matt S. McGlone; Dave B. McWethy; Cathy Whitlock (Global Change Biology, 2012)
At the time of M āori settlement, ca. 750 years ago, N ew Z ealand's ecosystems experienced catastrophic change, including the introduction of fire to ignition‐limited ecosystems and the resulting widespread loss of forest. While high‐resolution sediment‐charcoal analyses suggest this forest loss was rapid, M āori populations were small and transient during the Initial Burning Period and there is evidence for widespread fire activity in places where there is little archaeological evidence of human presence. These observations beg the question ‘how did small populations manage to transform large areas so rapidly?’ Using a simulation model, we demonstrate how the relationship between time since fire and flammability in N ew Z ealand's forests drives positive feedbacks that allow for rapid and extensive deforestation. Under ignition scenarios mirroring prehuman conditions, the model did not produce significant deforestation – thus, it is extremely unlikely that deforestation could have occurred without human‐initiated burning. Scenarios where ignition was spatio‐temporally random also failed to result in deforestation. Rapid and widespread forest loss occurred in scenarios incorporating spatio‐temporally savvy selection of ignition locations. Targeting ignitions in flammable vegetation was more important than targeting ignitions in years with favourable climatic conditions. However, targeting in space and time concurrently, such that flammable vegetation was ignited during favourable climatic years was the most efficient strategy of those simulated. Following the Initial Burning Period decadal ignitions would have been sufficient to maintain a deforested shrubland/grassland landscape. New Z ealand's Initial Burning Period is one of many that occurred across eastern Polynesia following human settlement, and these events have left long‐term legacy effects that remain evident in contemporary landscapes. Improving understanding of how humans shaped environments in N ew Z ealand in the past has implications for eastern P olynesia as a whole.

Soil Acid-Base Chemistry of a High-Elevation Forest Watershed in the Great Smoky Mountains National Park: Influence of Acidic Deposition - Meijun Cai; Amy M. Johnson; John S. Schwartz; Steve E. Moore; Matt A. Kulp (Water, Air, & Soil Pollution, 2012)

Partitioning Characteristics of Perfluorooctane Sulfonate Between Water and Foods - Feng Xiao; Matt F. Simcik; John S. Gulliver (Archives of Environmental Contamination and Toxicology, 2012)

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

An examination of the time course of training-induced skeletal muscle hypertrophy - Jason M. DeFreitas; Travis W. Beck; Matt S. Stock; Michael A. Dillon; Paul R. Kasishke (European Journal of Applied Physiology, 2011)

Dissolved Inorganic Nitrogen, Soluble Reactive Phosphorous, and Microbial Pollutant Loading from Tropical Rural Watersheds in Hawai'i to the Coastal Ocean During Non-Storm Conditions - Alexandria B. Boehm; Kevan M. Yamahara; Sarah P. Walters; Blythe A. Layton; Daniel P. Keymer; Rachelle S. Thompson; Karen L. Knee; Matt Rosener (Estuaries and Coasts, 2011)

Long-Term Annual and Seasonal Patterns of Acidic Deposition and Stream Water Quality in a Great Smoky Mountains High-Elevation Watershed - Meijun Cai; John S. Schwartz; R. Bruce Robinson; Stephen E. Moore; Matt A. Kulp (Water, Air, & Soil Pollution, 2011)

Chromosome 15q24-25.1 variants, diet, and lung cancer susceptibility in cigarette smokers - Lori C. Sakoda; Melissa M. Loomis; Jennifer A. Doherty; Marian L. Neuhouser; Matt J. Barnett; Mark D. Thornquist; Noel S. Weiss; Gary E. Goodman; Chu Chen (Cancer Causes & Control, 2011)

Non-uniform interhemispheric temperature trends over the past 550 years - Richard P. Duncan; Pavla Fenwick; Jonathan G. Palmer; Matt S. McGlone; Chris S. M. Turney (Climate Dynamics, 2010)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Grubbing by wild boars (Sus scrofa L.) and its impact on hardwood forest soil carbon dioxide emissions in Switzerland - Anita C. Risch; Sven Wirthner; Matt D. Busse; Deborah S. Page-Dumroese; Martin Schütz (Oecologia, 2010)

Long-Term Effects of Acidic Deposition on Water Quality in a High-Elevation Great Smoky Mountains National Park Watershed: Use of an Ion Input–Output Budget - Meijun Cai; John S. Schwartz; R. Bruce Robinson; Stephen E. Moore; Matt A. Kulp (Water, Air, & Soil Pollution, 2010)

Macronutrient (N, P, K) and Redoximorphic Metal (Fe, Mn) Allocation in Leersia oryzoides (Rice Cutgrass) Grown Under Different Flood Regimes - Samuel C. Pierce; Matt T. Moore; Dan Larsen; S. R. Pezeshki (Water, Air, & Soil Pollution, 2010)

Are treelines advancing? A global meta‐analysis of treeline response to climate warming - Melanie A. Harsch; Philip E. Hulme; Matt S. McGlone; Richard P. Duncan (Ecology Letters, 2009)
Treelines are temperature sensitive transition zones that are expected to respond to climate warming by advancing beyond their current position. Response to climate warming over the last century, however, has been mixed, with some treelines showing evidence of recruitment at higher altitudes and/or latitudes (advance) whereas others reveal no marked change in the upper limit of tree establishment. To explore this variation, we analysed a global dataset of 166 sites for which treeline dynamics had been recorded since 1900 AD. Advance was recorded at 52% of sites with only 1% reporting treeline recession. Treelines that experienced strong winter warming were more likely to have advanced, and treelines with a diffuse form were more likely to have advanced than those with an abrupt or krummholz form. Diffuse treelines may be more responsive to warming because they are more strongly growth limited, whereas other treeline forms may be subject to additional constraints.

Physiological Stress in Native Southern Brook Trout During Episodic Stream Acidification in the Great Smoky Mountains National Park - Keil J. Neff; John S. Schwartz; Theodore B. Henry; R. Bruce Robinson; Stephen E. Moore; Matt A. Kulp (Archives of Environmental Contamination and Toxicology, 2009)

Characterizing Episodic Stream Acidity During Stormflows in the Great Smoky Mountains National Park - Edwin B. Deyton; John S. Schwartz; R. Bruce Robinson; Keil J. Neff; Stephen E. Moore; Matt A. Kulp (Water, Air, & Soil Pollution, 2009)

Allochthonous litter inputs, organic matter standing stocks, and organic seston dynamics in upland Panamanian streams: potential effects of larval amphibians on organic matter dynamics - Checo Colón-Gaud; Scot Peterson; Matt R. Whiles; Susan S. Kilham; Karen R. Lips; Cathy M. Pringle (Hydrobiologia, 2008)

Biological Responses to Contrasting Hydrology in Backwaters of Upper Mississippi River Navigation Pool 25 - Michael B. Flinn; S. Reid Adams; Matt R. Whiles; James E. Garvey (Environmental Management, 2008)

Stable isotope characterization of mammalian predator–prey relationships in a South African savanna - Daryl Codron; Jacqui Codron; Julia A. Lee-Thorp; Matt Sponheimer; Darryl de Ruiter; James S. Brink (European Journal of Wildlife Research, 2007)

A pre‐deforestation pollen‐climate calibration model for New Zealand and quantitative temperature reconstructions for the past 18 000 years BP - Janet M. Wilmshurst; Matt S. McGlone; John R. Leathwick; Rewi M. Newnham (Journal of Quaternary Science, 2007)
Quantification of modern pollen rain–vegetation–climate relationships in New Zealand has been complicated by human destruction of at least 75% of the original forest cover since ca. 750 years BP, causing contemporary pollen rain over large areas to bear little resemblance to the pre‐human vegetation. We use a pre‐deforestation pollen database to circumvent this complication. The relationships between the pre‐deforestation pollen assemblages and six climatic variables were explored using principal components analysis and constrained regressions (redundancy analyses). Quantitative estimates of the most significant climate variable (mean annual temperature) were made at seven lowland to montane fossil pollen sites from throughout New Zealand using the modern analogue technique and a transfer function. These showed an initial increase in mean annual temperature after 18 000 cal. yr BP, a cooling at the time of the Antarctic Cold Reversal (centred on 13 500 cal. yr BP) and continuation of warming from ca. 12 000 cal. yr BP across the Younger Dryas chronozone, reaching a Holocene thermal optimum that may have been between 1.5 and 3°C warmer than present and lasted from 9000 to 7000 cal. yr BP depending on the site. Cooling to present‐day temperatures was well advanced by 4000–3000 cal. yr BP. Copyright © 2007 John Wiley & Sons, Ltd.

Stable isotope characterisation of mammalian predator–prey relationships in a South African savanna - Daryl Codron; Jacqui Codron; Julia A. Lee-Thorp; Matt Sponheimer; Darryl Ruiter; James S. Brink (European Journal of Wildlife Research, 2007)

Attenuation effect on seasonal basin-scale water storage changes from GRACE time-variable gravity - J. L. Chen; C. R. Wilson; J. S. Famiglietti; Matt Rodell (Journal of Geodesy, 2007)

Towards a climate event stratigraphy for New Zealand over the past 30 000 years (NZ‐INTIMATE project) - Brent V. Alloway; David J. Lowe; David J. A. Barrell; Rewi M. Newnham; Peter C. Almond; Paul C. Augustinus; Nancy A. N. Bertler; Lionel Carter; Nicola J. Litchfield; Matt S. McGlone; Jamie Shulmeister; Marcus J. Vandergoes; et al. (Journal of Quaternary Science, 2007)
It is widely recognised that the acquisition of high‐resolution palaeoclimate records from southern mid‐latitude sites is essential for establishing a coherent picture of inter‐hemispheric climate change and for better understanding of the role of Antarctic climate dynamics in the global climate system. New Zealand is considered to be a sensitive monitor of climate change because it is one of a few sizeable landmasses in the Southern Hemisphere westerly circulation zone, a critical transition zone between subtropical and Antarctic influences. New Zealand has mountainous axial ranges that amplify the climate signals and, consequently, the environmental gradients are highly sensitive to subtle changes in atmospheric and oceanic conditions. Since 1995, INTIMATE has, through a series of international workshops, sought ways to improve procedures for establishing the precise ages of climate events, and to correlate them with high precision, for the last 30 000 calendar years. The NZ‐INTIMATE project commenced in late 2003, and has involved virtually the entire New Zealand palaeoclimate community. Its aim is to develop an event stratigraphy for the New Zealand region over the past 30 000 years, and to reconcile these events against the established climatostratigraphy of the last glacial cycle which has largely been developed from Northern Hemisphere records (e.g. Last Glacial Maximum (LGM), Termination I, Younger Dryas). An initial outcome of NZ‐INTIMATE has been the identification of a series of well‐dated, high‐resolution onshore and offshore proxy records from a variety of latitudes and elevations on a common calendar timescale from 30 000 cal. yr BP to the present day. High‐resolution records for the last glacial coldest period (LGCP) (including the LGM sensu stricto ) and last glacial–interglacial transition (LGIT) from Auckland maars, Kaipo and Otamangakau wetlands on eastern and central North Island, marine core MD97‐2121 east of southern North Island, speleothems on northwest South Island, Okarito wetland on southwestern South Island, are presented. Discontinuous (fragmentary) records comprising compilations of glacial sequences, fluvial sequences, loess accumulation, and aeolian quartz accumulation in an andesitic terrain are described. Comparisons with ice‐core records from Antarctica (EPICA Dome C) and Greenland (GISP2) are discussed. A major advantage immediately evident from these records apart from the speleothem record, is that they are linked precisely by one or more tephra layers. Based on these New Zealand terrestrial and marine records, a reasonably coherent, regionally applicable, sequence of climatically linked stratigraphic events over the past 30 000 cal. yr is emerging. Three major climate events are recognised: (1) LGCP beginning at ca. 28 000 cal. yr BP, ending at Termination I, ca. 18 000 cal. yr BP, and including a warmer and more variable phase between ca. 27 000 and 21 000 cal. yr BP, (2) LGIT between ca. 18 000 and 11 600 cal. yr BP, including a Lateglacial warm period from ca. 14 800 to 13 500 cal. yr BP and a Lateglacial climate reversal between ca. 13 500 and 11 600 cal. yr BP, and (3) Holocene interglacial conditions, with two phases of greatest warmth between ca. 11 600 and 10 800 cal. yr BP and from ca. 6 800 to 6 500 cal. yr BP. Some key boundaries coincide with volcanic tephras. Copyright © 2007 John Wiley & Sons, Ltd.

β-Catenin regulation during matrigel-induced rat hepatocyte differentiation - Satdarshan P. S. Monga; Amanda Micsenyi; Matt Germinaro; Udayan Apte; Aaron Bell (Cell and Tissue Research, 2006)

Potential forest cover of New Zealand as determined by an ecosystem process model - Graeme M.J. Hall; Matt S. McGlone (New Zealand Journal of Botany, 2006)
A forest biome map for New Zealand is presented, based on the ecosystem process model LINKNZ. Climate surfaces, landforms, slope, and soil types defined 88 933 homogeneous landscape units covering the North and South islands (264000 km 2 ). Forest development (2000 years) was simulated on each unit with 78 individually param‐eterised species selected by ecological importance. Forest biomes for the units were assigned by the relative biomass predicted for 21 plant functional types, categorised from the available species. An assessment of model performance against a systematic sample of 559 measured forest plots was satisfactory (dissimilarity index = 0.25). Direct validation was not possible over most of the landscape where native forest has been removed, but performance was sensible against data from 136 pre‐deforesta‐tion pollen sites (dissimilarity index = 0.20). The modelled biome map reproduced the main characteristics of the current forest distribution in New Zealand and departures from the observed forest distribution were generally explained by omission of whole‐stand disturbance effects from simulations. The model reproduced lowland areas of the striking “beech gap” in the west‐central zone of the Southern Alps, but not the distribution of Noth‐ofagus species in montane areas of this zone. The most likely explanation supported previous conclusions that the absence was due to a slow reinvasion of Nothofagus after exclusion during the Last Glaciation. Predictions of Nothofagus across some regions of the south‐eastern South Island where it was nearly absent before settlement suggested that the ecological knowledge of some competing conifer species was incomplete.

Seasonal global mean sea level change from satellite altimeter, GRACE, and geophysical models - J. L. Chen; C. R. Wilson; B. D. Tapley; J. S. Famiglietti; Matt Rodell (Journal of Geodesy, 2005)

Corroded Pollen and Spores as Indicators of Changing Lake Sediment Sources and Catchment Disturbance - Janet M. Wilmshurst; Matt S. McGlone (Journal of Paleolimnology, 2005)

Macroinvertebrate communities in central Platte River wetlands: Patterns across a hydrologic gradient - Matt R. Whiles; Beth S. Goldowitz (Wetlands, 2005)

Goodbye Gondwana - Matt S. McGlone (Journal of Biogeography, 2005)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

Rapid development of phosphorus limitation in temperate rainforest along the Franz Josef soil chronosequence - Sarah J. Richardson; Duane A. Peltzer; Robert B. Allen; Matt S. McGlone; Roger L. Parfitt (Oecologia, 2004)

Winter leaf loss in the New Zealand woody flora - Matt S. McGlone; Roger J. Dungan; Graeme M.J. Hall; Robert B. Allen (New Zealand Journal of Botany, 2004)
Approximately 27 species (c. 5%) of the New Zealand woody flora have a marked loss of leaves in winter, although only 10 species are consistently fully deciduous and no extensive vegetation type is dominated by them. There are no summer deciduous species. The deciduous habit appears in most cases to have evolved independently within New Zealand from either ancestors or immigrants with short leaf life spans. New Zealand deciduous or semideciduous species typically lose substantial numbers of leaves throughout the growing season, and leaf loss is often gradual throughout winter but accelerated by frost. The deciduous habit in New Zealand tends to be a leaf‐ or shoot‐level feature reflecting short leaf life spans and winter stress on individual shoots, rather than a systematic feature of the canopy‐level organisation of the plant. Degree of deciduousness varies with taxon, plant age, climate, and soil fertility. A physiological study of co‐occurring fully deciduous ( Fuchsia excorticata ) and semideciduous ( Aristotelia serrata ) trees in the South Island established that higher growing‐season productivity of Fuchsia compensated for carbon gain forgone over winter. However, Fuchsia was significantly favoured over Aristotelia only on the coldest sites. Aside from some inland basins of the South Island, New Zealand has milder winters than those that favour deciduous taxa globally, and this is the primary reason for the low incidence of deciduous species. Even so, a number of deciduous species are common throughout. New Zealand deciduous trees and shrubs are typically fast growing and are characteristic of seral or forest marginal habitat on nutrient‐rich soils developed in recent alluvium or debris. The relatively low nutrient status of most New Zealand forest soils makes a deciduous phenology, with its necessarily high turnover of nutrients, less competitive than a nutrient‐conserving evergreen phenology. Deciduous species are often also divaricating, or have close relatives that are, and share a preference for nutrient‐rich soils with this growth form. This strong relationship between the two habits suggests both are, in part, adaptations to stressful climates by plants with high‐productivity leaves.

Recent spread of Dracophyllum scrub on subantarctic Campbell Island, New Zealand: climatic or anthropogenic origins? - Janet M. Wilmshurst; Kim L. Bestic; Colin D. Meurk; Matt S. McGlone (Journal of Biogeography, 2004)
Aim The vegetation of subantarctic Campbell Island consists mainly of lowland Dracophyllum scrub and upland tussock grassland and tundra. Soon after the island was discovered in 1810, occupation by sealers and whalers led to localized burning and cutting of scrub. Further burning and cutting took place as a result of sheep farming between 1894 and 1931. Since the earliest photographs and vegetation descriptions of the island in the late nineteenth century, scrub cover has expanded markedly. Also, since the 1960s, the island has become warmer and drier. The aim of this paper is to quantify scrub changes as depicted in photo‐sequences from the island, and to establish if the spread of scrub is a result of the cessation of anthropogenic activities or a response to global warming. Location Campbell Island, an isolated island 600 km south of New Zealand mainland (52°33.7′S, 169°09′E). Methods Changes in scrub cover in the island were established through analysis of 33 photographic sequences in the island, the earliest photos dating back to 1888. Visual estimates were made of percentage woody cover in matching areas of repeat photographs, and of changes in scrub distribution with altitude and landscape type. Results Dracophyllum scrub was restricted at the time of the first photographs (1888) relative to its present extent, and earlier written observations suggest that there had been little change from the 1840s. Scrub cover has subsequently increased in most areas. Most of the spread occurred after the cessation of farming. Change has mostly consisted of a thickening and expansion of pre‐existing scrub patches. There is no indication that the upper elevational limit of scrub has increased. Main conclusions Initial reduction of scrub was probably due to anthropogenic fire in the early nineteenth century, although it is possible that less favourable climates had also restricted its distribution. Failure of the scrub to regenerate significantly between 1840 and c. 1895 may also have been a consequence of generally cooler, wetter climates at this time. Rapid scrub expansion began between the end of farming and burning in 1931 and 1988 when the remaining feral sheep were removed. Sheep grazing in the absence of fire reduced competition, and encouraged regeneration and growth of woody scrub. Spread was probably assisted by a pronounced shift to warmer, drier climates in the second half of the twentieth century. Upper elevational limits of scrub have not increased, suggesting that factors other than summer temperature are controlling scrub line in this superoceanic environment.

Physical and genetic mapping of the rainbow trout major histocompatibility regions: evidence for duplication of the class I region - Ruth B. Phillips; Ana Zimmerman; Marc A. Noakes; Yniv Palti; Matt R. W. Morasch; Lisa Eiben; Sandra S. Ristow; Gary H. Thorgaard; John D. Hansen (Immunogenetics, 2003)

Holocene vegetation and climate change in southern New Zealand: linkages between forest composition and quantitative surface moisture reconstructions from an ombrogenous bog - Janet M. Wilmshurst; Matt S. McGlone; Dan J. Charman (Journal of Quaternary Science, 2002)
This paper presents a Holocene pollen record from an ombrotrophic bog in Southland, New Zealand, together with multiproxy data (testate amoebae, peat humification and plant macrofossils) from the same core to establish an independent semiquantitative record of peatland surface moisture. Linkages between reconstructed peatland surface moisture and regional forest composition are investigated using redundancy analysis of the forest pollen data constrained with predicted bog water‐table depths. Over 32% of the pollen data variance can be explained by surface moisture changes in the bog, suggesting a common cause of water‐table and regional vegetation change. Water tables were higher during the early to mid‐Holocene when the forest was dominated by podocarp taxa. Water tables lowered after about 3300 cal. yr BP coevally with the expansion of Nothofagus species, culminating with the dominance of Nothofagus subgenus Fuscospora in the past 1200 cal. yr BP. This is in apparent opposition to the warm/dry to cool/wet trend suggested by subjective interpretation of pollen data alone, from this and other studies. We suggest that during the late Holocene, drier summers associated with shifts in solar insolation caused reduced surface wetness and summer humidity, which together with a trend to cooler winters, apparently favoured the regeneration of Nothofagus species. Copyright © 2002 John Wiley & Sons, Ltd.

An ex vivo angiogenesis assay utilizing commercial porcine carotidartery: Modification of the rat aortic ring assay - Janet Stiffey-Wilusz; Judith A. Boice; John Ronan; Anthony M. Fletcher; Matt S. Anderson (Angiogenesis, 2001)

Absence of a seasonal cycle in the sonic neuromuscular system of the oyster toadfish - M. S. Johnson; T. D. Waybright; D.W. Matt; J. J. Feher; M. L. Fine (Journal of Fish Biology, 2000)
No seasonal pattern was found in total swimbladder weight, sonic muscle weight, or spinal sonic motor nucleus neuron soma size of the oyster toadfish Opsanus tau , indicating that additional nonsteroidal factors are also involved in the development of the toadfish sonic neuromuscular system.

Estimating past leaf-to-air vapour pressure deficit from terrestrial plant δ13C - Chris S. M. Turney; James Barringer; John E. Hunt; Matt S. McGlone (Journal of Quaternary Science, 1999)

A Holocene record of climate, vegetation change and peat bog development, east Otago, South Island, New Zealand - Matt S. Mcglone; Janet M. Wilmshurst (Journal of Quaternary Science, 1999)

A late Holocene history of natural disturbance in lowland podocarp/hardwood forest, Hawke's Bay, New Zealand - Janet M. Wilmshurst; Matt S. McGlone; Trevor R. Partridge (New Zealand Journal of Botany, 1997)
Palaeoecological investigations of sediment cores from two lake basins in the Tutira and Putere districts of Hawke's Bay demonstrate the impact of volcanic activity, fires, and storms on the vegetation and soil stability before human settlement and deforestation. A “disturbance curve” derived from the classification and ordination of pollen records, and correlated with charcoal and sediment records, illustrates relative forest disturbance over time. Before anthropogenic forest clearance in Hawke's Bay, forest composition fluctuated frequently as a result of disturbance from fires, droughts, and a major volcanic eruption. Each natural disturbance, indicated by short‐term increases of seral taxa, was followed by complete forest redevelopment. Cyclonic storms were not a major cause of disturbance to lowland podocarp/hardwood forests in the region, nor to the bracken‐scrubland vegetation that replaced the forest after clearance. However, storms scoured and rapidly transported riverbank sediments into the lake basins. Compared with the preceding natural disturbances, deforestation by early Maori settlers represents a type and magnitude of disturbance previously unrecorded in the cores.

Increased moth herbivory associated with environmental stress of pinyon pine at local and regional levels - N. S. Cobb; S. Mopper; Catherine A. Gehring; Matt Caouette; Kerry M. Christensen; Thomas G. Whitham (Oecologia, 1997)

Use of the Intestinal Bile Acid Transporter for the Uptake of Cholic Acid Conjugates with HIV-1 Protease Inhibitory Activity - Matts Kågedahl; Peter W. Swaan; Carl T. Redemann; Mary Tang; Charles S. Craik; Francis C. Szoka; Svein Øie (Pharmaceutical Research, 1997)